Self-assembly, surface-modified substrate and method for producing same
By employing mesogenic parts connected via polymer chains in a self-organizing manner, the limitations of traditional self-assembly methods are overcome, enabling highly ordered structures with controlled molecular arrangements.
Patent Information
- Application Number
- JP2020059131
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-09
- Filing Date
- 2020-03-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-03-27
Smart Images

Figure 0007618156000037 
Figure 0007618156000038 
Figure 0007618156000039
Abstract
Description
[Technical field]
[0001] The present invention relates to a self-organized body, a surface-modified substrate, and a method for producing the same. [Background technology]
[0002] In recent years, in the fields of integrated circuit elements, field effect transistors, liquid crystal display elements, photoelectric conversion elements, nonlinear optical elements, two-dimensional magnetic materials, drug delivery systems, biophysical chemistry, and the like, there is a demand for nano-order materials having a uniform and highly ordered structure with controlled molecular arrangement. Nano-order materials having a structure with at least one dimension of a few hundred nm or less are called nanomaterials. Recently, a technique for producing nanomaterials using a bottom-up self-organization technique in which atoms or molecules are assembled one by one and the organization, orientation, or arrangement is precisely controlled has attracted much attention.
[0003] One example of self-organization technology is the Langmuir-Blodgett method (LB method). A monolayer formed on the surface of a liquid such as water by the LB method is transferred to the surface of a solid and stacked in any number of layers, which is called a Langmuir-Blodgett film (LB film). The monolayer film on the surface of the liquid before being transferred to the solid surface is called a Langmuir film (L film). The L film and LB film have the great advantage that a film of one layer of regularly arranged and oriented molecules can be formed on a subphase, and the film thickness on the molecular order and the orientation or arrangement of the molecules can be controlled simultaneously. Therefore, the LB method is one of the most effective methods for obtaining organic ultrathin films with ordered structures at the nano level.
[0004] Conventional Langmuir-Layer films and LB films are made by dispersing amphiphilic molecules (e.g., fatty acids) that mainly have hydrophilic and hydrophobic parts in polar solvents such as water. Therefore, three factors are important in governing the properties of Langmuir-Layer films and LB films: (i) the degree of affinity of the hydrophilic parts for water, (ii) the cohesive force acting between hydrophobic interactions, and (iii) the relative ratio of the hydrophilic parts to the hydrophobic parts. Various research and development efforts are being conducted on the molecular design of amphiphilic molecules that consider these factors.
[0005] However, although the LB method is very promising as a self-organization technique having an ordered structure at the nano level, the degree of freedom in molecular design is limited due to the constraint of a chemical structure showing amphiphilicity. In addition, with the recent development of nanotechnology, a technique that can design a highly ordered structure using molecules other than amphiphilic molecules is required. For example, Patent Document 1 discloses a technique for aligning liquid crystal molecules that are not amphiphilic molecules in a desired direction. Specifically, Patent Document 1 discloses a technique in which a liquid crystal compound having reactive groups at both ends is arranged on an alignment film that has been rubbed in a specific direction, and then the liquid crystal compound homogeneously aligned in the specific direction is brought into contact with a substrate, and the reactive groups at both ends are reacted with the substrate, thereby producing a liquid crystal compound homogeneously aligned in the specific direction on the surface of the substrate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2012-51862 A Summary of the Invention [Problem to be solved by the invention]
[0007] In the above Patent Document 1, it is used as a "mold" to control the molecular alignment of the rubbed alignment film. Therefore, not only is it difficult to uniformly adjust the height of the rubbing groove so that one molecule of liquid crystal compound can fit in it, but rubbing unevenness also occurs. Therefore, the technology of Patent Document 1 has a problem in that it is difficult to form a highly ordered structure with a controlled molecular alignment. Therefore, an object of the present invention is to provide a self-organized body having a highly ordered structure in which the molecular arrangement is controlled, a surface-modified substrate having the self-organized body on its surface, and methods for producing the same. [Means for solving the problem]
[0008] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that the above-mentioned problem can be solved by having a plurality of long mesogen portions linked via polymer chains, and by self-organizing the mesogen portions so that they are aligned in a direction intersecting with the director of the mesogen portions, thereby completing the present invention. Effect of the Invention
[0009] According to the present invention, it is possible to provide a self-organized body having a highly ordered structure in which the molecular arrangement is controlled, a surface-modified substrate having the self-organized body on its surface, and methods for producing the same. [Brief description of the drawings]
[0010] [Figure 1A] FIG. 1A is a schematic cross-sectional view showing an example of a development and film-forming apparatus used in the Langmuir-Blodgett method. [Figure 1B] FIG. 1B is a schematic diagram showing a polymerizable liquid crystal compound having elongated mesogen moieties. [Diagram 2] FIG. 2 is a flow chart showing an example of a method for producing a self-organized structure according to the present invention. [Diagram 3] FIG. 3 is a flow chart showing another example of the method for producing a self-organized structure according to the present invention. [Figure 4A]FIG. 4A is a flow chart showing one embodiment of a method for producing a self-organized body according to the present invention. [Figure 4B] FIG. 4B is a flow chart showing another embodiment of the method for producing a self-organized body according to the present invention. [Figure 4C] FIG. 4C is a flow chart showing another embodiment of the method for producing a self-organized body according to the present invention. [Figure 4D] FIG. 4D is a flow chart showing another embodiment of the method for producing a self-organized body according to the present invention. [Diagram 5] FIG. 5 is a diagram showing a schematic configuration of a DRLM (reflective polarizing microscope) and a UV lamp (ultraviolet light irradiator) used in the polymerization step, which were used in Example 1. As shown in FIG. [Figure 6] FIG. 6 is an image observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step in Example 1. [Figure 7] Figure 7 is a set of images observed with a reflective polarizing microscope, showing the change over time in the ordered structure of a self-organized body (membrane) from before UV light irradiation to 40 seconds after UV light irradiation in the self-organized body manufacturing process (polymerization process) of Example 3. [Figure 8] FIG. 8 is an image observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step in Example 4. [Figure 9] FIG. 9 is an image observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step in Example 5. [Figure 10] FIG. 10 is an image observed by a reflective polarizing microscope, showing the state of the self-assembled body after the polymerization step in Example 5. [Figure 11] FIG. 11 is an image of the L film before the polymerization step in Example 6, observed with a reflective polarizing microscope. [Figure 12] FIG. 12 is an image observed by a reflective polarizing microscope, showing the state of the self-assembled body after the polymerization step in Example 6. [Figure 13] FIG. 13 is an image observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step in Example 7. [Figure 14]FIG. 14 shows experimental results showing the irradiation time dependence of reflected light intensity under various ultraviolet irradiation conditions in the polymerization step of producing a self-assembled body of Example 9 (polymerization step). [Figure 15] FIG. 15 shows the experimental results showing the relationship between the surface pressure and the molecular occupation area in the self-assembled body produced in Example 10. [Figure 16] FIG. 16 is a set of images observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step for each molecular occupation area A in Example 11. [Figure 17] FIG. 17 is a schematic diagram showing the relationship between the molecular occupancy area and the pretilt angle. [Figure 18] FIG. 18 shows the experimental results showing the relationship between the relaxation time and the molecular occupation area in the production process (polymerization process) of the self-assembled body of Example 12. [Figure 19] FIG. 19 is an image observed by a reflective polarizing microscope, showing the state of the L film before the polymerization step in Example 13. [Figure 20] FIG. 20 shows the experimental results showing the relationship between the intensity of irradiated reflected light and the molecular occupation area in the manufacturing process (polymerization process) of the self-assembled body of Example 14. [Figure 21] Figure 21 shows a group of images of the texture of the L film of Example 16 observed with a Brewster angle microscope at various times after the start of UV irradiation (100s: 100 seconds after the start of UV irradiation, 180s: 180 seconds after the start of UV irradiation). [Figure 22A] FIG. 22A shows a group of images of the textures of the L membranes of Example 17, prepared by varying the molecular occupancy area (0.283 nm2, 0.248 nm2, 0.220 nm2) before and after polymerization, observed with a Brewster angle microscope. [Figure 22B] FIG. 22B shows a group of images of the textures of the L films of Example 17 prepared by varying the molecular occupancy area (0.198 nm 2 , 0.170 nm 2 , 0.157 nm 2 ) before and after polymerization, observed with a Brewster angle microscope. [Diagram 23]FIG. 23 is an image showing the state of the L film in Example 18 observed by a reflective polarizing microscope. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention relates to a self-organized body having a plurality of long mesogen moieties bonded via polymer chains, the mesogen moieties being self-organized so as to be aligned in a direction intersecting with the directors of the mesogen moieties.
[0012] The self-organized body according to the present invention has a plurality of mesogen parts, and therefore is easily able to form an ordered structure. The self-organized body according to the present invention has an ordered structure in which the director direction of a plurality of long mesogen parts, i.e., the average direction of the long direction of the mesogen parts, intersects with the direction in which the mesogen parts are arranged. Therefore, the self-organized body according to the present invention has an ordered structure in which the arrangement direction in which the mesogen parts are arranged is not parallel to the long direction of the mesogen parts (in other words, the structure is not one in which a plurality of mesogen parts are arranged linearly in one dimension along the long direction of the mesogen parts). The self-organized body has an ordered structure in which the long direction of the mesogen parts has a predetermined angle (=90°-(pretilt angle described later)) with respect to the arrangement direction in which the mesogen parts are arranged, and the mesogen parts are arranged two-dimensionally. The structure in which the mesogen parts are arranged two-dimensionally can be transformed into various shapes. Therefore, the self-organized body according to the present invention has a two-dimensional or three-dimensional structure.
[0013] The ordered structure of the self-organized body according to the present invention will be described with reference to a diagram showing an example of a manufacturing method for the self-organized body described later. As shown in FIG. 1B and S2 in FIG. 2, liquid crystal molecules 2 having a structure in which molecular chains 4a, 4b are extended outward from both ends of the mesogen portion 3 are assembled, and the mesogen portions 3 are aligned in the X direction and self-organized. The self-organized body 10 has a plurality of long mesogen portions 3 bonded via a polymer chain L, and has a structure in which the one-dimensional or two-dimensional direction in which the plurality of mesogen portions 3 are aligned (for example, the XY plane in FIG. 2) and the director direction of the mesogen portions 3 (for example, the Z direction in FIG. 2) intersect. For convenience of explanation, FIG. 2 shows a state in which the direction in which the plurality of mesogen portions 3 are aligned and the director direction of the mesogen portions 3 (the longitudinal direction of the mesogen portions) are perpendicular to each other. However, in the self-assembled body 10 according to the present invention, the longitudinal direction (Z direction) of the mesogen portions 3 may have a predetermined angle with respect to the arrangement direction (one-dimensional or two-dimensional direction, for example, the XY plane in FIG. 2) in which the mesogen portions 3 are arranged. In addition, in FIG. 2, for convenience of explanation, the mesogen portions 3 are connected to each other by one polymer chain L, but the mesogen portions 3 may be connected to each other by two or more polymer chains L. When the mesogen portions 3 are connected to each other by one polymer chain L, a two-dimensional linear polymer tends to be formed. On the other hand, when the mesogen portions 3 are connected to each other by multiple polymer chains L, a film-like structure or a network structure tends to be formed.
[0014] In this specification, the term "self-organization" refers to a concept that combines "self-assembly" and "dissipative structure." In addition, the term "dissipative structure" refers to an ordered structure that appears in a non-equilibrium open system and is formed spontaneously by destabilizing a thermodynamically stable equilibrium structure. In addition, the term "self-assembly" refers to a highly ordered structure formed by the assembly of molecules or atoms near equilibrium conditions. Therefore, in this specification, the term "self-organized body" refers to a substance in which the assembly state of mesogen parts has at least one of the above-mentioned ordered structures, and the shape or form of the substance is not particularly limited. Furthermore, unless there is a specific restrictive description for the term "self-organized body", such as "after polymerization" or "bonded (or linked) via polymer chains", "self-organized body" includes nanomaterials consisting of multiple molecules such as two-dimensional linear polymers, supramolecules (including micelles, vesicles, colloids, etc.), layered substances, membranes (including L-type membranes, LB membranes, and multilayer molecular membranes formed at air-liquid interfaces (on the liquid surface)), polymer aggregates (including two-dimensional linear polymer aggregates), and membranous fragments, as well as reactants formed by chemical reactions (e.g., polymerization reactions) between the molecules that make up these nanomaterials.
[0015] The "mesogen moiety" in this specification includes known mesogen moieties such as elongated, discoid, bent (= banana-shaped), etc. In this specification and the drawings, for the sake of convenience, a elongated mesogen moiety is described as an example, but the scope of the present invention is not limited thereto.
[0016] In this specification, the term "polymer chain" refers to a chain-like or mesh-like polymer formed by polymerization of polymerizable groups at the ends of the raw material polymerizable liquid crystal compound and / or (non-liquid crystal) polymerizable compound. The constituent parts of the "polymerizable liquid crystal compound" referred to here are the mesogen part and the polymerizable group, and may contain a molecular chain (spacer) as necessary. In the polymer chain, the mesogen part exists in the main chain or in the side chain.
[0017] A typical L film, LB film, or colloid is formed by a balance between hydrophilicity and hydrophobicity between amphiphilic molecules having hydrophilic and hydrophobic groups and a solvent. On the other hand, the present invention does not require hydrophilic and hydrophobic groups, and utilizes the phenomenon in which the attractive force acting between mesogen parts is the main cause of molecular assembly. In other words, the attractive interaction acting mainly between mesogen parts lowers the free energy of the molecular assembly, thereby realizing the self-organized assembly of the present invention. Therefore, one of the characteristics of the self-organized assembly of the present invention is that liquid crystal molecules having mesogen parts form a self-organized assembly based on their liquid crystal properties, without requiring amphiphilic molecules. Therefore, the L film and the LB film in this specification are not limited to films formed from amphiphilic molecules.
[0018] The mesogen part in the present invention may have an end directly bonded to a polymerizable group, or may have a chain-like molecular chain (spacer) at the end. When the mesogen part has a chain-like molecular chain (spacer), the polymerizable group and the mesogen part may be bonded via the chain-like molecular chain (spacer). The chain-like molecular chain may be linear or branched, and it is preferable that the mesogen parts are connected to each other via the molecular chain. Examples of the chain-like molecular chain (spacer part) include an alkyl group having 1 to 50 carbon atoms (one CH2 group or two or more non-adjacent CH2 groups present in the alkyl group may be independently replaced by -O-, -COO-, -OCO-, or -OCO-O-, and a hydrogen atom in the alkyl group may be replaced by a polymerizable group represented by the general formula (P) described later).
[0019] The mesogen portion and polymer chain, which are the components of the self-organized body according to the present invention, will be described below.
[0020] In the present invention, it is preferable that the mesogen part itself exhibits liquid crystallinity. Incidentally, the term "exhibiting liquid crystallinity" means that the mesogen part has a rod-like rigid portion and exhibits orientation. Therefore, in this specification, the "mesogen part" means a group that is easy to induce structural order and can induce the behavior of a liquid crystal phase. The "mesogen part" typically includes a skeleton formed by a plurality of rigid skeletons such as cyclic groups such as aromatic rings being bonded in a (straight) line shape directly or via a linking group. Furthermore, the "liquid crystal phase" referred to here refers to a phase that has both the fluidity of a liquid and the anisotropy of a crystal, and includes nematic liquid crystal, smectic liquid crystal, cholesteric liquid crystal, discotic liquid crystal, and the like. In addition, in the self-organized body, the mesogen parts may all have the same mesogen skeleton, or may have two or more different mesogen skeletons.
[0021] The mesogen moiety in the present invention preferably has a skeleton in which two or more cyclic groups are linearly bonded directly or via a linking group.
[0022] Specifically, the mesogen portion is preferably represented by the following general formula (Me).
[0023] [ka]
[0024] (In the above general formula (Me), B11, B12 and B13 each independently represent a 1,4-phenylene group, a 1,4-cyclohexylene group, a 1,4-cyclohexenyl group, a tetrahydropyran-2,5-diyl group, a 1,3-dioxane-2,5-diyl group, a tetrahydrothiopyran-2,5-diyl group, a 1,4-bicyclo(2,2,2)octylene group, a decahydronaphthalene-2,6-diyl group, a pyridine-2,5-diyl group, a pyrimidine -2,5-diyl group, pyrazine-2,5-diyl group, thiophene-2,5-diyl group-, 1,2,3,4-tetrahydronaphthalene-2,6-diyl group, 2,6-naphthylene group, phenanthrene-2,7-diyl group, 9,10-dihydrophenanthrene-2,7-diyl group, 1,2,3,4,4a,9,10a-octahydrophenanthrene-2,7-diyl group, 1,4-naphthylene group, benzo[1,2-b:4,5-b']dithio phene-2,6-diyl group, benzo[1,2-b:4,5-b']diselenophene-2,6-diyl group, [1]benzothieno[3,2-b]thiophene-2,7-diyl group, [1]benzoselenopheno[3,2-b]selenophene-2,7-diyl group, or fluorene-2,7-diyl group, and one or more of F, Cl, CF3, OCF3, CN group, or alkyl group having 1 to 8 carbon atoms (wherein each of the hydrogen atoms in the alkyl group is 1, or more phenyl groups, and one CH2 group or two or more non-adjacent CH2 groups in this group may be replaced independently by -O-, -COO-, -OCO- or -OCO-O-.), an alkoxy group, an alkanoyl group, an alkanoyloxy group, an alkenyl group having 2 to 8 carbon atoms, an alkenyloxy group, an alkenoyl group, an alkenoyloxy group, and / or a group represented by the general formula (P):
[0025] [ka]
[0026] (In the above general formula (P), P 10 represents a polymerizable functional group, Sp 10 represents an alkylene group having 1 to 18 carbon atoms; X10 represents -O-, -COO-, -OCO-, -OCH2-, -CH2O-, -CH2CH2OCO-, or -CH2CH2COO-; q 10 represents 0 or 1, q 11 represents 0 or 1. (However, P 10 -Sp 10 , and Sp 10 -X 10 does not include -OO-, -O-NH-, -SS- and -OS- groups; Z11 and Z12 each independently represent -COO-, -OCO-, -CH2CH2-, -OCH2-, -CHO-, -CH=CH-, -C≡C-, -CH=CHCOO-, -OCOCH=CH-, -CH2CH2COO-, -CH2CH2OCO-, -COOCH2CH2-, -OCOCH2CH2-, -CONH-, -NHCO-, -CH=N-, -N=CH-, -CH=NN=CH-, an alkylene group having 2 to 10 carbon atoms which may have a halogen atom, or a single bond; r1 represents 0, 1 or 2, and when there are a plurality of B11 and Z11, they may be the same or different, and * in the above formula represents a molecular chain, a polymer chain, a carbon atom, or a bond to another atom.
[0027] In addition, the mesogen portion preferably has a linear molecular chain at both ends, and the linear molecular chain is preferably a part of a polymer chain or an alkylene group having 1 to 30 carbon atoms (one CH2 group or two or more non-adjacent CH2 groups present in this group may each be independently replaced by -O-, -COO-, -OCO- or -OCO-O-).
[0028] The polymer chain in the present invention is preferably a molecular chain having a repeating unit, and the molecular structure and type of the repeating unit are not particularly limited as long as it connects the mesogen parts to each other. Therefore, the polymer chain may be a straight chain type, a branched type, a star type, a comb type, a random type, a graft type, a network type, or a crosslinked structure. The polymer chain may have one or more types of repeating units. The polymer chain preferably has a repeating unit derived from an ethylenically unsaturated monomer. The polymer chain is not limited to having a hydrophilic group or a hydrophobic group. Depending on the solvent used in producing the self-organized body of the present invention, a hydrophilic group and / or a hydrophobic group may be introduced into the polymer chain as necessary. For example, the weight average molecular weight (Mw) of the polymer chain is preferably 500 to 500,000, and more preferably 1,000 to 300,000. In other words, the polymer chain in the present invention is preferably composed of a repeating unit derived from a polymerizable liquid crystal compound and / or a (non-liquid crystal) polymerizable compound used in producing the self-organized body. The polymer chain in the present invention is more preferably a polymer substantially composed of repeating units derived from the monomers of general formula (1) and a non-liquid crystal polymerizable compound described below. Here, "substantially" means that the total of the repeating units derived from the monomers of general formula (1) and a non-liquid crystal polymerizable compound present in the polymer exceeds 50% by weight, and the total of the repeating units derived from the monomers of general formula (1) and a non-liquid crystal polymerizable compound is preferably 70% by weight or more.
[0029] The self-assembled body of the present invention has either a structure in which a mesogen moiety is introduced into the main chain of a polymer chain, a structure in which a mesogen moiety is introduced into the side chain of a polymer chain, or a structure in which a mesogen moiety is introduced into both the main chain and the side chain of a polymer chain.
[0030] In the present invention, it is preferable that the long mesogen moiety has an optical axis in the long direction, which allows the self-organized body according to the present invention to be used as an optical material.
[0031] When the present invention is a self-assembled monolayer, the optical effect can be suppressed as much as possible due to the extremely thin monolayer. Therefore, the birefringence of the self-assembled monolayer is small, and it is considered to be suitable for use in applications where birefringence is not required or where low birefringence is preferable. For example, when the self-assembled monolayer is used as an alignment film, it has the advantage that the phase difference caused by the birefringence of the alignment film itself can be ignored.
[0032] In a preferred embodiment of the present invention, the self-organized body is a film, and it is preferable that the plane direction of the film intersects with the director of the mesogenic portion, and the mesogenic portions are self-organized so as to be aligned in the plane direction of the film.
[0033] The self-assembly of the present invention is preferably an L film, an LB film, or a multilayer molecular film. Therefore, the self-assembly of the present invention is preferably a film having a plurality of long mesogen parts bonded via polymer chains, in which the surface direction of the film body and the directors of the mesogen parts intersect, and the mesogen parts are self-assembled so as to be aligned in the surface direction of the film body.
[0034] When the self-organized body is a film, it has an ordered structure in which the director direction of a plurality of long mesogen moieties, i.e., the average direction of the long dimension directions of the mesogen moieties, intersects with the direction in which the mesogen moieties are arranged (the plane direction of the film). Therefore, the self-organized body according to the present invention has an ordered structure in which the arrangement direction in which the mesogen moieties are arranged (the plane direction of the film) is not parallel to the long dimension direction of the mesogen moieties. The self-organized body has an ordered structure in which the long dimension direction of the mesogen moieties has a predetermined angle (=90°-(pretilt angle below)) with respect to the arrangement direction in which the mesogen moieties are arranged, and the mesogen moieties are arranged two-dimensionally.
[0035] An example of an ordered structure in the case where the self-organized body according to the present invention is a film body will be described with reference to FIG. 1B and FIG. 17 described in the Examples below. As shown in FIG. 1B and FIG. 17(a) and (b), a liquid crystal molecule 2 having a mesogen portion 3 and molecular chains 4a and 4b self-organizes to form a self-organized body on a substrate 1 so as to be aligned in a plurality of rows. Although FIG. 17(a) and (b) do not show that the mesogen portion 3 is bonded via a polymer chain, in this embodiment, at least one of the molecular chains 4a and 4b may be linked by a polymer chain. In addition, in this specification, the angle formed by the molecular long axis direction (director of the mesogen portion 3) and the normal direction of the substrate 1 is defined as the "pretilt angle" (pretilt angle βa or βb in FIG. 17) based on the normal direction perpendicular to the direction in which the mesogen portions 3 are arranged (the surface direction of the film body or the surface direction of the substrate 1). In this case, in this embodiment, it is preferable that the self-assembled body, which is a film body, has an ordered structure in which multiple long mesogenic portions 3 are self-assembled together so that the pretilt angle (βa or βb) is less than 90°, and the mesogenic portions 3 are bonded via polymer chains.
[0036] Furthermore, the self-assembly of the present invention may have a structure in which two or more of the above-mentioned films are laminated, if necessary. When the self-assembly is a film, the lamination direction in which the two or more films are laminated is preferably a direction intersecting the direction in which the mesogen parts are arranged, i.e., a structure in which the films are laminated along the (approximate) director direction of the mesogen parts. This makes it possible to provide a self-assembly having a more highly ordered structure in which the molecular arrangement is controlled.
[0037] The method for producing a self-organized structure of the present invention will now be described. The method for producing the self-organized body of the present invention preferably applies the Langmuir-Blodgett method. Typical Langmuir-Blodgett methods include the vertical immersion method and the horizontal attachment method. The former vertical immersion method is a method that includes a step (A) of producing an L-film on a polar solvent by dropping a developing solution (= composition) in which a substance to be self-organized (e.g., fatty acid) is dissolved in an organic solvent onto a polar solvent such as water and evaporating the organic solvent, and compressing the polar solvent surface on which the molecules are developed two-dimensionally to compress the L-film, and a step (B) of moving a solid substrate up and down through the polar solvent surface on which the molecules are developed while maintaining an appropriate surface pressure.
[0038] The latter horizontal adhesion method is a method having a step (C) of placing the substrate surface almost parallel to the polar solvent surface while maintaining an appropriate surface pressure after the step (A) and contacting the substrate surface with the polar solvent surface. In addition, a modified version of the horizontal adhesion method is a method having a step (D) of placing the substrate surface almost parallel to the polar solvent surface after the step (A) and removing only the polar solvent (for example, by draining it from the bottom) and contacting the substrate with the monomolecular film on the polar solvent. Then, by repeating the process of the vertical immersion method or the horizontal adhesion method (including modified versions), a so-called lamination step (or accumulation step) of laminating (or accumulating) monomolecular films can be performed, in which an arbitrary number of monomolecular films are transferred one by one onto the substrate, and an organic thin film with an arbitrary number of layers can be produced.
[0039] As a method for producing a self-organized body of the present invention, any of the above-mentioned Langmuir-Blodgett methods may be applied.
[0040] The method for producing a self-organized body according to the present invention includes a spreading step of spreading a polymerizable liquid crystal compound having a long-shaped mesogen portion in a polar solvent, and a polymerization step of polymerizing the polymerizable liquid crystal compound. The method for producing a self-organized body according to the present invention preferably further includes a holding step and / or a recovery step, which will be described in detail below, as necessary. The method for producing a self-organized body according to the present invention may further include a lamination step of laminating (also referred to as accumulation) a self-organized body in which a plurality of the long-shaped mesogen portions are bonded via polymer chains by the polymerization step, as necessary. The method for producing a self-organized body according to the present invention will be described below for each step.
[0041] The method for producing a self-assembled body according to the present invention includes a spreading step of spreading a polymerizable liquid crystal compound having long mesogen portions on a polar solvent.
[0042] When the polymerizable liquid crystal compound of the present invention is spread on the surface of a polar solvent, the polymerizable liquid crystal compounds tend to self-organize due to their liquid crystal structure so as to reduce the contact area with the polar solvent, forming an L film, which is a so-called aggregate. At that time, a specific liquid crystal phase is exhibited depending on the molecular structure, such as the structure of the mesogen part of the polymerizable liquid crystal compound, the structure of the spacer, such as the length of the spacer, or the combination of the structure of the mesogen part and the structure of the spacer.
[0043] The method for forming such an L film is not particularly limited, and a spreading method used in a general Langmuir-Blodgett method can be adopted in the present invention. Hereinafter, a flow from the spreading step to film formation will be described using an example of a spreading / film formation device used in a general Langmuir-Blodgett method. FIG. 1A is a cross-sectional view that shows a schematic diagram of an apparatus for forming an L film or an LB film. The spreading / film formation device that can be used for producing a self-assembled monolayer in the present invention is not limited to the device shown in FIG. 1A. The apparatus shown in FIG. 1A has been used for preparing L or LB films, and includes a rectangular parallelepiped trough 100 with one side open, a polar solvent 105 as a developing solvent filled in the trough 100, a polymerizable liquid crystal compound or a polymerizable composition 103 developed on the liquid surface of the polar solvent 105 (or the polar solvent surface), a movable bar 101 that can slide on the liquid surface of the polar solvent 105 at a predetermined speed, an outlet 104 that can discharge the polar solvent 105 to the outside, which is attached to the bottom of the trough 100, a substrate 102 immersed in the polar solvent 105, and a mounting table 106 having a flat surface on which the substrate 102 can be placed. The trough 100 serves as a pool for storing the polar solvent 105, and generally has a length and width of about 10 cm to 1 m. Generally, water is mainly used as the polar solvent 105. The movable bar 101 is an example of a first holding mechanism described later, a movable body for compressing the molecules spread on the liquid surface of the polar solvent, and is controlled from the outside to move at a predetermined speed. In the spreading step, while the movable bar 101 is moved in the -X axis direction, a polymerizable liquid crystal compound or a polymerizable composition 103 is dropped or sprayed by a syringe or the like filled therein.
[0044] The method of operating the spreading / film-forming apparatus is to fill the trough 100 with an appropriate amount of polar solvent 105, drop the polymerizable liquid crystal compound or polymerizable composition 103 onto the liquid surface of the polar solvent 105, and spread it over the entire liquid surface of the polar solvent 105. Thereafter, as will be described in the recovery process and the like described later, the movable bar 101 is slid in the +X-axis direction while adjusting the moving speed of the movable bar 101 so that the surface pressure detected by a surface pressure detection device (not shown) becomes constant, thereby compressing the polymerizable liquid crystal compound or polymerizable composition 103, and the substrate 102 is moved in a direction perpendicular to the liquid surface of the polar solvent 105, thereby transferring and / or accumulating the L film. Examples of the spreading / film-forming apparatus include a fully automatic LB film preparation apparatus HBM 700LB (manufactured by Kyowa Interface Science Co., Ltd.). In FIG. 1A, for convenience of explanation, the vertical immersion method is described as an example of the Langmuir-Blodgett method, but the L film may be transferred and / or accumulated on the substrate 102 using a known horizontal attachment method. Furthermore, there is a modified horizontal attachment method. The modified example will be described below with reference to FIG. 1A. A mounting table 106 having a flat surface on which the substrate 102 can be mounted is immersed in the trough 100 so that the height h1 of the mounting table 106 from the bottom of the trough 100 is higher than the height h2 of the discharge port 104. Then, the substrate 102 is submerged so that the surface of the substrate 102 is in contact with the flat surface on the mounting table 106 in the trough 100 and is completely immersed in the polar solvent 105, and then the polymerizable liquid crystal compound or polymerizable composition 103 is spread on the liquid surface of the polar solvent 105 to form an L film, and the polar solvent 105 is discharged from the discharge port 104, and the surface of the substrate 102 may be coated with an L film or an LB film. By using this method, it is possible to reduce the molecular flow in the L-type membrane, and thus to produce a self-assembled body having a highly ordered structure with a more controlled molecular arrangement. In addition, the polymerization step described below can be carried out at any time after the spreading step.
[0045] If necessary, the L film may be compressed during or after the formation of the L film to obtain an L film in which the polymerizable liquid crystal compound 103 is densely packed on the polar solvent surface. For example, after the polar solvent is evaporated or dissolved, the L film can be compressed at a constant speed using a movable bar 101 to obtain an L film in which the polymerizable liquid crystal compound 103 and a non-liquid crystal polymerizable compound added as required are densely packed on the polar solvent 105 surface. By compressing the L film, it can be adjusted to a solid condensed film or a liquid condensed film.
[0046] In the spreading step of the present invention, in order for the polymerizable liquid crystal compound having a long mesogen portion to come into contact with a polar solvent and spread, the surface tension of the polar solvent is increased by γ s (vector), the surface tension of the polymerizable liquid crystal compound is γ c (vector), and the interfacial tension between the polar solvent and the polymerizable liquid crystal compound is γ sc (vector), the diffusion coefficient S is expressed by the following formula (1). 1 is preferably 0 or greater.
[0047]
number
[0048] Diffusion coefficient S 1 When the value of the saturation constant is 0 or more, the polymerizable liquid crystal compound is easily spread on the surface of the polar solvent.
[0049] When it is difficult to directly spread the polymerizable liquid crystal compound in a polar solvent, a polymerizable composition containing a first solvent and a polymerizable liquid crystal compound may be prepared in advance as necessary, and the polymerizable composition may be dropped onto the polar solvent. The polymerizable composition in the present invention contains one or more polymerizable liquid crystal compounds, and may contain a first solvent, a non-liquid crystal polymerizable compound, a known non-polymerizable liquid crystal compound, or a known additive as necessary. For example, when a polymerizable composition containing a first solvent is dropped into a polar solvent, the first solvent evaporates or dissolves in the polar solvent, and the polymerizable liquid crystal compound spreads on the polar solvent to form an L film containing the polymerizable liquid crystal compound.
[0050] If necessary, the polymerizable composition may further contain a non-liquid crystal polymerizable compound. That is, in the spreading step in the present invention, it is preferable to spread a polymerizable composition containing a polymerizable liquid crystal compound having a long mesogen portion and a first solvent and / or a non-liquid crystal polymerizable compound added as necessary on a polar solvent. As a result, the first solvent in the polymerizable composition dropped on the polar solvent evaporates or dissolves in the polar solvent, and the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound added as necessary spread on the polar solvent to form an L film containing the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound added as necessary. Therefore, when the spreading step is performed using the polymerizable composition, the surface tension of the polar solvent is set to γ s (vector), the surface tension of the polymerizable composition is γ rc (vector), and the interfacial tension between the polar solvent and the polymerizable composition is γ src (vector), the diffusion coefficient S is expressed by the following formula 2 is preferably 0 or greater.
[0051]
number
[0052] In the developing step of the present invention, when a first solvent and / or a non-liquid crystal polymerizable compound is used, a polymerizable composition containing a polymerizable liquid crystal compound may be developed. When such a polymerizable composition is used, the first solvent, the second solvent described below, the non-liquid crystal polymerizable compound, a polymerization initiator, a polymerization inhibitor, an antioxidant, an ultraviolet absorber, a chain transfer agent, or a sensitizer may be included in the polymerizable composition as necessary within a range that does not impair the effects of the present invention. These components and the polymerizable liquid crystal compound, non-liquid crystal polymerizable compound, and polar solvent used in the present invention will be described later.
[0053] The method for producing a self-assembled body according to the present invention includes a polymerization step of polymerizing a polymerizable liquid crystal compound. By polymerizing the polymerizable liquid crystal compound, the mesogen parts are bonded to each other via a polymer chain, and the self-assembled state of the mesogen parts is fixed. Therefore, the self-assembled state is easier to maintain than the conventional monolayer L film, and a self-assembled body having a highly ordered structure with controlled molecular alignment can be produced.
[0054] The timing for polymerizing the polymerizable liquid crystal compound may be when the polymerizable liquid crystal compound is in contact with the polar solvent, or the self-assembled polymerizable liquid crystal compound may be polymerized after the L film is transferred onto a substrate, such as in the holding step or recovery step described below.
[0055] The polymerization step in the present invention is preferably a step of polymerizing the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is in contact with a polar solvent. By carrying out the polymerization step in a state where the polymerizable liquid crystal compound is in contact with a solvent, a self-organized body having a highly ordered structure with a more controlled molecular arrangement can be produced. In the conventional preparation of LB films, as described above, regardless of the technique, a method is generally used in which an L film is prepared on the surface of a solvent and transferred to a substrate, and then the LB film is polymerized. Therefore, in the conventional LB method, problems have been confirmed in which the molecular arrangement or molecular orientation of the aggregate is disturbed due to the unevenness of the surface shape or surface characteristics such as unevenness of the substrate surface, and further due to the accumulation process involving flow. However, in a preferred embodiment of the present invention, by carrying out the polymerization step in a state where the polymerizable liquid crystal compound is in contact with a polar solvent, the shape or surface characteristics of the substrate surface are not affected, and therefore a self-organized body having a highly ordered structure with a more controlled molecular arrangement can be produced. That is, in the present invention, it can be said that a highly ordered self-organized polymerized film (self-organized body) without defects can be produced by polymerization on a perfectly uniform plane without unevenness in comparison with a solid substrate.
[0056] Therefore, the polymerization process in the present invention is preferably a process in which the polymerizable liquid crystal compound and the polar solvent are brought into contact with each other on the surface of the polar solvent, and the polymerizable liquid crystal compound is polymerized in a state in which the polymerizable liquid crystal compound is spread on the surface.
[0057] The polymerization operation of the polymerizable liquid crystal compound of the present invention is preferably carried out by generally irradiating with light such as ultraviolet light or heating in a state where the polymerizable liquid crystal compound is in contact with the surface of a substrate or in a state where the polymerizable liquid crystal compound is in contact with a polar solvent. When polymerization is carried out by light irradiation, specifically, irradiation with active energy rays (e.g., ultraviolet light) of 400 nm or less is preferable, and irradiation with light of a wavelength of 250 to 370 nm is most preferable. However, in cases where active energy rays of 300 nm or less cause decomposition of components contained in the polymerizable composition such as the polymerizable liquid crystal compound or the non-liquid crystal polymerizable compound, it may be preferable to carry out the polymerization treatment with active energy rays of 300 nm or more. This light is preferably diffused light and unpolarized light.
[0058] The irradiation intensity of the active energy rays used in the polymerization step is 0.1 mW / m 2 ~500mW / m 2 In particular, the range of 0.2 mW / m 2 ~250mW / m 2 The active energy ray intensity is preferably in the range of 0.1 mW / m 2 If the power is less than 500mW / m, it will take a long time to complete the polymerization. 2 At an intensity exceeding this, the liquid crystal molecules may tend to be photodecomposed, or a large amount of polymerization heat may be generated, causing an increase in temperature during polymerization.
[0059] The temperature during irradiation with active energy rays is set to a temperature at which the polymerizable liquid crystal compound of the present invention can maintain a liquid crystal phase, and is preferably set to 30°C or less as much as possible in order to avoid the induction of thermal polymerization of the polymerizable liquid crystal compound. In addition, the polymerizable liquid crystal compound or the polymerizable composition containing the polymerizable liquid crystal compound usually undergoes a phase transition in the order of Cr(crystal)N(nematic)I(isotropic liquid) during the temperature rise process, and shows a liquid crystal phase of only a nematic phase. However, in the case of the polymerizable liquid crystal compound of the present invention, since it has a characteristic of exhibiting smectic liquid crystallinity (including hexatic liquid crystallinity), during the temperature rise process, it shows a phase transition of Cr(crystal)Sm(smectic)N(nematic)-I(isotropic liquid), and shows two liquid crystal phases, a smectic phase and a nematic phase. On the other hand, during the temperature drop process, since it is in a thermodynamically non-equilibrium state, it may not crystallize and may maintain a nematic liquid crystal state or a smectic liquid crystal state even below the Cr(crystal)N(nematic) or Cr(crystal)Sm(smectic) transition temperature. This state is called a supercooled state. In the present invention, a polymerizable liquid crystal compound in a supercooled state is also included in a state in which the liquid crystal phase is maintained. Since the smectic phase has a layer structure and has a structure closer to a crystal than the nematic phase, a self-organized body obtained by irradiating ultraviolet light in the smectic phase state is preferred over a self-organized body obtained by irradiating ultraviolet light in the nematic phase state, because the self-organized body has an ordered structure closer to a crystal, and therefore has improved orientation order and / or heat resistance.
[0060] Furthermore, if necessary, a mask can be used to polymerize only specific regions by irradiating them with active energy rays, and then the orientation state of the unpolymerized portions can be changed by applying an electric field, a magnetic field, temperature, or the like, and then the unpolymerized portions can be polymerized to obtain a self-organized body having multiple regions with different orientation directions.
[0061] The method for producing a self-assembled body according to the present invention preferably further comprises a holding step of holding the mesogen part of the polymerizable liquid crystal compound in a self-assembled state by a first holding mechanism before or after the polymerization step, thereby making it possible to provide a self-assembled body having a highly ordered structure in which the molecular alignment of the liquid crystal molecules is more controlled.
[0062] This holding step is a step for maintaining the ordered structure of the mesogen part of the self-assembled polymerizable liquid crystal compound, and does not include a so-called polymerization step for fixing the mesogen part by a polymerization reaction. Specifically, the holding step includes a step of transferring (or removing) an aggregate or self-organized body of the mesogen part of the polymerizable liquid crystal compound self-organized to a first holding mechanism such as a substrate before or after the polymerization step, or a step of compressing the aggregate or self-organized body of the polymerizable liquid crystal compound at a constant speed using the first holding mechanism such as the movable bar before or after the polymerization step.
[0063] Therefore, the first holding mechanism may be the above-mentioned slidable movable bar or a base material. The surface of the movable bar may be coated with a fluororesin to suppress adhesion of the polymerizable liquid crystal compound.
[0064] In the holding step of the present invention, it is preferable to transfer the self-organized polymerizable liquid crystal compound before polymerization and / or the self-organized polymerizable liquid crystal compound formed by polymerizing the self-organized polymerizable liquid crystal compound to the substrate by immersing the substrate in a polar solvent. In addition, as another embodiment of the holding step of the present invention, it is preferable to directly transfer the self-organized polymerizable liquid crystal compound before polymerization and / or the self-organized polymerizable liquid crystal compound formed by polymerizing the self-organized polymerizable liquid crystal compound to the substrate. This makes it possible to provide a self-organized structure having a highly ordered structure in which the molecular arrangement is more controlled. Furthermore, the surface of the substrate can be modified by the self-organized polymerizable liquid crystal compound and / or the self-organized polymerizable liquid crystal compound formed by polymerizing the self-organized polymerizable liquid crystal compound.
[0065] In the present invention, the substrate that can be used is not particularly limited, and a desired material can be used, and it may be an inorganic substrate or an organic substrate. For example, the former inorganic substrate may be a silicon wafer, an ITO, a gallium arsenide plate, a quartz plate, a glass substrate, a ceramic plate, a calcium fluoride plate, etc. On the other hand, the latter organic substrate may be a PMMA substrate, a polyamide substrate, a polysulfone substrate, a polyester substrate, a polycarbonate substrate, a fluororesin substrate, a polyimide substrate, a polyethersulfone substrate, a PEEK substrate, a PPS substrate, or a polyphenylene oxide substrate.
[0066] In the present invention, when a substrate is used, the substrate surface may be subjected to either hydrophilic treatment or hydrophobic treatment using a known pretreatment method before coating with the self-organized body, if necessary. Examples of the pretreatment include silane treatment, ultrasonic cleaning treatment, acid treatment, alkali treatment, and plasma treatment. For example, as a silane treatment, the surface of a silicon substrate may be pretreated with a silane coupling agent such as dimethyldichlorosilane, hexamethylsilazane, or octyltrichlorosilane. In addition, the silane treatment is classified into a hydrophobic treatment and a reactive functional group treatment, and can be appropriately selected according to the purpose.
[0067] The method for producing a self-assembly according to the present invention may further include a step of recovering the self-assembly in which a plurality of long mesogen moieties are bonded via polymer chains, obtained by the polymerization step. For the recovery step, a known recovery method can be appropriately selected depending on the form of the obtained self-assembly and the intended use of the obtained self-assembly.
[0068] That is, when the obtained self-organized body is a two-dimensional linear polymer, the two-dimensional linear polymer itself may be directly scooped and collected without using a substrate, or the above-mentioned LB method may be adopted using a substrate. Alternatively, a method may be used in which a solution containing the two-dimensional linear polymer and a polar solvent as a developing solvent is poured into a dialysis membrane bag having a desired pore size, and then the dialysis membrane bag is immersed in another desired solvent to exchange the solvent with the solvent in the dialysis membrane, and then the solution is collected in a solution state. Furthermore, a method may be used in which the solution containing the two-dimensional linear polymer and the polar solvent as a developing solvent or the solution after the above-mentioned solvent exchange is freeze-dried.
[0069] Furthermore, when the self-assembled product is a film, the film itself may be directly scooped up and collected without using a substrate, or the film may be attached to the surface of a substrate using the Langmuir-Blodgett technique described above and then collected.
[0070] Furthermore, when the obtained self-organized body is a supramolecule such as a colloid or micelle, a method can be used in which a solution containing the supramolecule and a polar solvent to be developed is injected into a dialysis membrane bag having a desired pore size, the dialysis membrane bag is immersed in another desired solvent to exchange the solvent, and then the solution is recovered.
[0071] A preferred embodiment of the method for producing a self-organized body according to the present invention will be described below with reference to the drawings. The method for producing a self-organized body according to the present invention is roughly classified into two types depending on the timing of performing the polymerization step. That is, the method is classified into a method in which a polymerizable liquid crystal compound (or a polymerizable composition) is spread on a polar solvent surface, the polymerizable liquid crystal compound self-organizes on the polar solvent and forms an aggregated state as an L-film, and then the self-organized body obtained by the polymerization step is transferred to a substrate or the like to be collected (the first embodiment below), and a method in which a polymerizable liquid crystal compound (or a polymerizable composition) is spread on a polar solvent surface, the polymerizable liquid crystal compound self-organizes on the polar solvent and forms an aggregated state as an L-film, and then the self-organized body is transferred to a substrate in a state where the polymerizable liquid crystal compound self-organizes on the polar solvent and forms an aggregated state as an L-film, and then the holding step is performed to hold the aggregated state, and then the polymerization step is performed on the substrate to collect the self-organized body (the second embodiment below).
[0072] A first embodiment of a method for producing a self-organized body according to the present invention includes a spreading step of spreading a polymerizable liquid crystal compound having a long mesogen portion in a polar solvent, a polymerization step of polymerizing the polymerizable liquid crystal compound while the polymerizable liquid crystal compound and the polar solvent are in contact with each other on the surface of the polar solvent and the polymerizable liquid crystal compound is spread on the surface, and a recovery step of recovering the substrate coated with the self-organized body by immersing the substrate in the polar solvent or by attaching the self-organized body obtained by the polymerization step onto the substrate.
[0073] Hereinafter, the first embodiment will be described with reference to FIG. 2. A polymerizable liquid crystal compound 2 (or a polymerizable composition) having a mesogen portion 3 and molecular chains 4a and 4b is spread on the liquid surface of a polar solvent 5 to form an L film (step 1: S1). In this case, the L film formed on the liquid surface of the polar solvent 5 is in contact with air 7. The molecular chain 4a has a polymerizable group (for example, the following general formula (P)). Then, in the state of step 1, the polymerizable liquid crystal compound 2 is irradiated with UV light to perform a polymerization process (step 2: S2). As a result, a polymerization reaction progresses to form a polymer chain L connecting the mesogen portions 3 to each other, and a self-organized body 10 in which a plurality of long mesogen portions 3 are bonded via the polymer chain L is produced on the liquid surface of the polar solvent 5. Then, the substrate 1, which has been immersed in the polar solvent 5 in advance, is pulled up into the air 7 (step 3: S3), and the self-organized body 10 is attached to the surface of the substrate 1, thereby producing a surface-modified substrate in which the surface of the substrate 1 is covered with the self-organized body 10 (step 4: S4). Then, if necessary, steps S1 to S4 can be repeated using a surface-modified substrate in which the surface of the substrate 1 is coated with the self-assembled structure 10, to prepare an LB film in which a plurality of layers are accumulated. The accumulated number is 1 to 100 layers, preferably 1 to 80 layers, preferably 1 to 50 layers, preferably 1 to 30 layers, preferably 1 to 20 layers, more preferably 1 to 15 layers, and more preferably 1 to 10 layers. In addition, a polymerizable liquid crystal compound and / or a known non-polymerizable liquid crystal compound having a different composition from the LB film already formed may be accumulated and coated.
[0074] As described above, in the method of the first embodiment, the polymerization step is performed in a state where the polymerizable liquid crystal compound and the polar solvent are in contact with each other, so that the shape or surface properties of the substrate surface are not affected, and therefore a self-organized body having a highly ordered structure with a more controlled molecular alignment can be produced. In particular, when the polymerization step is performed after the polymerizable liquid crystal compound is spread on the liquid surface of the polar solvent to form an L film, the liquid surface of the polar solvent can be regarded as an ideal plane, so that it is considered that molecular flow can be reduced as much as possible, and therefore a self-organized body having a highly ordered structure with a more controlled molecular alignment of the liquid crystal molecules can be produced.
[0075] In addition, for convenience of explanation, an embodiment using the vertical immersion method has been described in Fig. 2, but other methods (horizontal attachment method, etc.) described above may also be used. Furthermore, for convenience of explanation, an example in which a polymerizable group is formed on the molecular chain 4a linked to the mesogen portion 3 has been described in Fig. 2, but if necessary, a polymerizable group may also be formed on the molecular chain 4b, and the polymerizable group may be polymerized.
[0076] A second embodiment of the method for producing a self-organized body according to the present invention includes a developing step of developing a polymerizable liquid crystal compound having long mesogen portions in a polar solvent, a holding step of transferring the self-organized polymerizable liquid crystal compound to a substrate by immersing the substrate in the polar solvent, a polymerization step of polymerizing the polymerizable liquid crystal compound transferred to the substrate, and a recovery step of recovering the substrate having a surface covered with a self-organized body in which a plurality of long mesogen portions obtained by the polymerization step are bonded via polymer chains.
[0077] The second embodiment will be described below with reference to FIG. 3. A polymerizable liquid crystal compound 2 (or a polymerizable composition) having a mesogen portion 3 and molecular chains 4a and 4b is spread on the liquid surface of a polar solvent 5 to form an L film (step 11: S11). In this case, the L film formed on the liquid surface of the polar solvent 5 is in contact with air 7. The molecular chain 4a has a polymerizable group (for example, the following general formula (P)). Then, the substrate 1, which has been immersed in the polar solvent 5 in advance, is pulled up into the air 7 (step 12: S12), so that the L film is attached to the surface of the substrate 1. With the L film attached to the surface of the substrate 1, the polymerizable liquid crystal compound 2 is irradiated with UV light to perform a polymerization process (step 13: S3). As a result, a polymerization reaction progresses to form a polymer chain L that connects the mesogen portions 3 to each other, and a self-organized body 10 in which a plurality of long mesogen portions are bonded via a polymer chain is produced on the surface of the substrate 1 (step 14: S4). Then, if necessary, steps S11 to S14 can be repeated using a surface-modified substrate in which the surface of the substrate 1 is covered with the self-organized structure 10, thereby producing an LB film in which a plurality of layers are accumulated.
[0078] In the method of the second embodiment, the polymerization step is performed in a state where the polymerizable liquid crystal compound is in contact with the substrate, and therefore the molecular arrangement is easily disturbed due to the influence of the shape or surface characteristics of the substrate surface. However, the manufacturing method itself is simple and has excellent manufacturing efficiency.
[0079] The third embodiment is a modified example of the first embodiment described above. As shown in FIG. 4A, the third embodiment shows an example of a manufacturing method using two types of polymerizable liquid crystal compounds having different chemical structures, that is, a polymerizable liquid crystal compound 2' (or a polymerizable composition) dropped in a region D1 on the liquid surface of the polar solvent 5, and a polymerizable liquid crystal compound 2 (or a polymerizable composition) dropped in a region D2 on the liquid surface of the polar solvent 5. As shown in FIG. 4A, the polymerizable liquid crystal compound 2' (or a polymerizable composition) has a polymerizable group (for example, the following general formula (P)) on both molecular chains 4a' and 4b'. On the other hand, the polymerizable liquid crystal compound 2 (or a polymerizable composition) has a polymerizable group (for example, the following general formula (P)) only on the molecular chain 4a. In addition, the polymerizable liquid crystal compound 2' (or a polymerizable composition) is dropped in a region D1 on the liquid surface of the polar solvent 5, and the polymerizable liquid crystal compound 2 (or a polymerizable composition) is dropped in a region D2 on the liquid surface of the polar solvent 5, with the substrate 1 as a boundary, to perform a development process. Then, after each monolayer (L film) is formed on the polar solvent 5, the polymerizable liquid crystal compound 2' (or polymerizable composition) and the polymerizable liquid crystal compound 2 (or polymerizable composition) are irradiated with UV light to perform a polymerization process. This allows the polymerization reaction to proceed, forming a polymer chain L, and a self-organized body can be formed on the liquid surface of the polar solvent 5. At this time, since the polymerizable liquid crystal compound 2' having two or more polymerizable groups is used in the region D1, a self-organized body in which the mesogen parts are bonded via a plurality of polymer chains L is formed. If necessary, a polymerizable composition in which a non-liquid crystal polymerizable compound is mixed with the polymerizable liquid crystal compound 2' is developed to form a self-organized body having a film-like structure or a network structure. On the other hand, since the polymerizable liquid crystal compound 2 having one polymerizable group is used in the region D2, a self-organized body having a lower crosslink density than the self-organized body formed in the region D1 is formed. At this time, if necessary, a non-liquid crystal polymerizable compound may also be mixed in the region D1. Then, the operation of lowering the self-organized bodies formed on both sides of the substrate 1 at a predetermined speed from the air into the polar solvent 5 and then raising the self-organized bodies from the polar solvent 5 into the air at a predetermined speed can be repeated any number of times to accumulate the self-organized bodies layer by layer on the substrate 1, thereby obtaining the desired LB film.In the present invention, an LB film may be accumulated that adheres only when the substrate 1 is raised, or an LB film may be accumulated that adheres only when the substrate 1 is lowered. If necessary, each surface of the substrate 1 may be previously subjected to a surface treatment such as a hydrophobic treatment or a hydrophilic treatment.
[0080] 4A shows an example in which two types of polymerizable liquid crystal compounds 2 and 2' are partitioned across the substrate 1 to form different self-assemblies on both sides of the substrate 1. However, as a modification of the third embodiment, the same polymerizable liquid crystal compound may be used on both sides across the substrate 1, or the polymerizable liquid crystal compound 2' may be developed only in the region D1 or region D2 of the substrate 1 to form a self-assembly.
[0081] The fourth embodiment is an aspect of a manufacturing method in which a polymerization step is performed before the L film is attached to the substrate surface, similarly to the first embodiment and the third embodiment. The fourth embodiment is a method in which a self-organized body formed by polymerizing a polymerizable liquid crystal compound 2 (or a polymerizable composition) is attached to the surface of the substrate 1 by lowering the substrate 1 from the air into a polar solvent 5 at a predetermined speed. More specifically, as shown in FIG. 4B, a required amount of the polymerizable liquid crystal compound 2 (or a polymerizable composition) is dropped onto the liquid surface of the polar solvent 5, a polymerization step is performed on the L film formed on the polar solvent 5, and after the self-organized body is formed, the self-organized body is attached to the substrate 1 by an operation of lowering the substrate 1 from the air into the polar solvent 5 at a predetermined speed, thereby obtaining an LB film.
[0082] After recovering the base material 1 having a surface covered with the precipitated self-organized bodies, the same operation can be repeated to accumulate the self-organized bodies on the base material 1 layer by layer.
[0083] The fifth embodiment is an aspect of a manufacturing method in which a polymerization step is performed before the L film is attached to the substrate surface, similarly to the first embodiment, the third embodiment, and the fourth embodiment. As shown in FIG. 4C, the fifth embodiment is a method of obtaining an LB film by dropping a required amount of a polymerizable liquid crystal compound 2 (or a polymerizable composition) onto the liquid surface of a polar solvent 5, performing a polymerization step on the L film formed on the polar solvent 5 to form a self-organized body, and then dropping the self-organized body from the air into the polar solvent 5 at a predetermined speed so that the self-organized body adheres to the substrate 1, thereby attaching the self-organized body to the substrate 1 in one layer. In the fifth embodiment, a movable bar 6 is provided, and the polymerizable liquid crystal compound 2 spread on the liquid surface of the polar solvent 5 can be compressed as necessary. In addition, the movable bar 6 can partition the spread position of the polymerizable liquid crystal compound 2 in the trough, and the substrate 1 coated with the self-organized body on the surface can be collected by sandwiching the movable bar 6. After collecting the substrate 1 coated with the self-organized body on the surface, the same operation can be repeated to accumulate the self-organized body on the substrate 1 one layer at a time.
[0084] The third to fifth embodiments are modified versions of the first embodiment. That is, the third to fifth embodiments are embodiments in which the polymerization step is performed in a state where the polymerizable liquid crystal compound is in contact with the polar solvent. If necessary, the timing of the polymerization step in the third to fifth embodiments may be changed so that the polymerizable liquid crystal compound is transferred to a substrate in a state where it is in an aggregated state as an L film, and then the polymerization step is performed on the substrate, as in the second embodiment.
[0085] In a preferred embodiment of the method for producing a self-organized body according to the present invention, after the spreading step, it is preferable to have a polymerization step of polymerizing the polymerizable liquid crystal compound while the polymerizable liquid crystal compound is in contact with the polar solvent, and a recovery step of recovering the substrate having the self-organized body on its surface by attaching the self-organized body formed by the polymerization step to a surface of the substrate.
[0086] In another preferred embodiment of the method for producing a self-organized body according to the present invention, after the spreading step, it is preferable to have a polymerization step of immersing a substrate in a polar solvent having a polymerizable liquid crystal compound spread on its surface to attach the polymerizable liquid crystal compound to the substrate surface, and then polymerizing the polymerizable liquid crystal compound in a state in which the polymerizable liquid crystal compound is in contact with the polar solvent, and a recovery step of recovering the substrate having, on its surface, a self-organized body in which a plurality of the long mesogen portions are bonded via polymer chains by the polymerization step.
[0087] A preferred embodiment (sixth embodiment) will be described below with reference to FIG. 4D. As shown in FIG. 4D, the substrate 1 is fed in the direction of the arrow in FIG. 4D by a feed roll, and the trough is filled with a polar solvent 5. The polymerizable liquid crystal compound 2 is spread on the liquid surface of the polar solvent 5, forming an L film. Furthermore, a part of the substrate 1 is immersed in the polar solvent 5 on whose surface the polymerizable liquid crystal compound 2 is spread. Also, in FIG. 4D, the polymerization process can be performed at two points: UV irradiation 1 that enables the polymerization of the polymerizable liquid crystal compound 2 before the self-assembled polymerizable liquid crystal compound 2 is attached to the surface of the substrate 1, and UV irradiation 2 that enables the polymerization of the polymerizable liquid crystal compound 2 after the self-assembled polymerizable liquid crystal compound 2 is attached to the surface of the substrate 1. In either case of UV irradiation, the polymerizable liquid crystal compound 2 and the polar solvent 5 are in contact with each other. Also, the UV irradiation 2 is described as a form in which polymerization is performed in the polar solvent 5.
[0088] Therefore, one embodiment of the manufacturing method of the present invention includes a polymerization step of polymerizing the polymerizable liquid crystal compound 2 in a state where the polymerizable liquid crystal compound 2 and the polar solvent 5 are in contact with each other by UV irradiation 2 after the polymerizable liquid crystal compound 2 is applied to the surface of the substrate 1 sent from the right side to the left side in Fig. 4D, and a recovery step of recovering the substrate 1 from the left side, the substrate 1 having on its surface a self-organized body in which a plurality of long mesogen parts are bonded via polymer chains formed by the polymerization step. In another embodiment of the manufacturing method of the present invention, the substrate 1 having on its surface a self-organized body in which a plurality of long mesogen parts are bonded via polymer chains formed by the polymerization step is polymerized in a state where the polymerizable liquid crystal compound 2 and the polar solvent 5 are in contact with each other by UV irradiation 1 before the polymerizable liquid crystal compound 2 is applied to the surface of the substrate 1 sent from the right side to the left side in Fig. 4D, and a recovery step of recovering the substrate 1 from the left side, the substrate 1 having on its surface a self-organized body in which a plurality of long mesogen parts are bonded via polymer chains formed by the polymerization step. Furthermore, in another embodiment of the manufacturing method of the present invention, the method includes a first polymerization step of polymerizing the polymerizable liquid crystal compound 2 in a state in which the polymerizable liquid crystal compound 2 and the polar solvent 5 are in contact with each other by UV irradiation 1 before the polymerizable liquid crystal compound 2 is attached to the surface of the substrate 1 sent from the right side to the left side in Figure 4D, a second polymerization step of polymerizing the polymerizable liquid crystal compound 2 in a state in which the polymerizable liquid crystal compound 2 and the polar solvent 5 are in contact with each other by UV irradiation 2, and a recovery step of recovering the substrate 1 from the left side, the substrate 1 having on its surface a self-organized body in which a plurality of long mesogen moieties are bonded via polymer chains, formed by the first and second polymerization steps.
[0089] In one embodiment of the manufacturing method of the present invention, the polymerizable liquid crystal compound 2 may be polymerized by UV irradiation 1 and / or UV irradiation 2 in a state where the polymerizable liquid crystal compound 2 is in contact with the polar solvent 5. When emphasis is placed on the viewpoint of producing a self-assembled body having a highly ordered structure in which the molecular alignment of the liquid crystal molecules is more controlled by minimizing molecular flow, it is preferable to polymerize the self-assembled polymerizable liquid crystal compound 2 by UV irradiation 1 before the polymerizable liquid crystal compound 2 is attached to the surface of the substrate 1. On the other hand, when emphasis is placed on manufacturing efficiency, it is preferable to polymerize the self-assembled polymerizable liquid crystal compound 2 by UV irradiation 2 after the polymerizable liquid crystal compound 2 is attached to the surface of the substrate 1.
[0090] 4D, a movable bar 6 is provided, and the polymerizable liquid crystal compound 2 spread on the liquid surface of the polar solvent 5 may be compressed as necessary. Furthermore, the polymerizable liquid crystal compound 2 may be spread on both sides of the substrate 1, and the polymerized polymerizable liquid crystal compound 2 or an L film of the polymerizable liquid crystal compound 2 may be attached to both sides of the substrate 1.
[0091] As another embodiment other than the above-mentioned first to sixth embodiments, it is preferable to have a step of spreading a polymerizable liquid crystal compound having a long mesogen portion between a polar solvent and a second solvent that is phase-separated from the polar solvent, and a polymerization step of polymerizing the spread polymerizable liquid crystal compound. As described in Example 13 below, the above method involves placing a substrate at the bottom of a trough in advance, and then pouring in a mixed liquid (a second solution containing a polar solvent and a second solvent different from the polar solvent) in an amount sufficient to completely immerse the substrate. In this case, it is preferable that the second solvent is not dissolved in the polar solvent. Then, after the polymerizable liquid crystal compound or the polymerizable composition is spread at the interface between the polar solvent and the second solution, the polymerization step is carried out. In this case, the above-mentioned holding step may be carried out before or after the polymerization, as necessary. Also, instead of the above-mentioned second solvent, a solution containing the second solvent and a known additive may be used.
[0092] In the present invention, whether or not an LB film is formed as a self-assembled body can be confirmed by measuring the molecular occupancy area (A) per molecule calculated from the film area (hereinafter also simply referred to as molecular occupancy area) and the surface pressure (π) in the L film, which is the precursor of the LB film. That is, in order to form an LB film, it is preferable that the surface pressure of the L film, which is the precursor, is in the range for forming a solid condensed film. From the viewpoint of forming a multi-layered accumulated film, the surface pressure is preferably 5 to 20 mN / m, and more preferably 10 to 20 mN / m. Furthermore, when the self-organized body according to the present invention is formed from an L film, the order of the liquid crystal state, i.e., the molecular assembly state, can be changed by controlling the molecular occupation area of the L film or the amount of the polymerizable composition spread.
[0093] The self-assembled body of the present invention can be applied in various fields, such as protective films for optical elements and magnetic heads, alignment films, surface modification, and surface coatings for various materials.
[0094] The best mode of the polymerizable composition according to the present invention will be described below. In the present invention, the polymerizable composition exhibits "liquid crystallinity". The term "exhibiting liquid crystallinity" means that the polymerizable composition exhibits liquid crystallinity in a state in which the organic solvent is removed after the polymerizable composition is applied to a substrate. In the present invention, the "liquid crystal" of the polymerizable liquid crystal compound means that the polymerizable liquid crystal compound exhibits liquid crystallinity when used alone, or when mixed with other liquid crystal compounds to form a mixture. The polymerizable composition can be polymerized by performing a polymerization treatment by irradiation with light such as ultraviolet light, heating, or a combination of these.
[0095] The polymerizable liquid crystal compound in the present invention is not particularly limited as long as it has a long mesogen part and a polymerizable group. The polymerizable liquid crystal compound used in the present invention is not particularly limited as long as it shows liquid crystallinity alone or in a composition with other compounds and has at least one polymerizable functional group, and any known and commonly used compound can be used.
[0096] For example, Handbook of Liquid Crystals (edited by D. Demus, J. W. Goodby, G. W. Gray, H. W. Spiess, and V. Vill, published by Wiley-VCH, 1998), Quarterly Chemistry Review No. 22, Chemistry of Liquid Crystals (edited by the Chemical Society of Japan, 1994), or Japanese Patent Application Laid-Open Nos. 7-294735, 8-3111, 8-29618, 11-80090, 11-116538, and 11-116668, and Japanese Patent Application Laid-Open Nos. 11-11671 and 11-11687 are known. Examples of such a compound include rod-shaped polymerizable liquid crystal compounds having a rigid portion called a mesogen in which a plurality of structures such as 1,4-phenylene group and 1,4-cyclohexene group are linked together, and a polymerizable functional group such as a vinyl group, an acrylic group, or a (meth)acrylic group, as described in JP-A-2004-2373 and JP-A-2004-99446, and rod-shaped polymerizable liquid crystal compounds having a maleimide group, as described in JP-A-2004-2373 and JP-A-2004-99446. Among these, rod-shaped liquid crystal compounds having a polymerizable group are preferred, since they are easy to prepare liquid crystals having a temperature range that includes low temperatures around room temperature.
[0097] Specifically, the polymerizable liquid crystal compound in the present invention is preferably a compound represented by the following general formula (1).
[0098] [ka]
[0099] (In the above general formula (1), P 11 represents a polymerizable functional group, Sp 1 represents an alkylene group having 1 to 18 carbon atoms (a hydrogen atom in the alkylene group may be substituted with one or more halogen atoms, a CN group, or an alkyl group having 1 to 8 carbon atoms and having a polymerizable functional group represented by the following general formula (1-a), and one CH group or two or more non-adjacent CH groups present in this group may be each independently replaced with -O-, -COO-, -OCO-, or -OCO-O-), X 11-O-, -S-, -OCH2-, -CH2O-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO -, -SCH2-, -CH2S-, -CF2O-, -OCF2-, -CF2S-, -SCF2-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=C represents H-, -OCO-CH=CH-, -COO-CH2CH2-, -OCO-CH2CH2-, -CH2CH2-COO-, -CH2CH2-OCO-, -COO-CH2-, -OCO-CH2-, -CH2-COO-, -CH2-OCO-, -CH=CH-, -N=N-, -CH=NN=CH-, -CF=CF-, -C≡C- or a single bond, q1 represents 0 or 1, MG represents a mesogenic group, R 11 represents a hydrogen atom, a halogen atom, a cyano group, or a linear or branched alkyl group having 1 to 12 carbon atoms, the alkyl group may be linear or branched, and in the alkyl group, one -CH2- or two or more non-adjacent -CH2- may each be independently replaced by -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, or R 11 is represented by the following general formula (1-a)
[0100] [ka]
[0101] (In the above general formula (1-a), P 12 represents a polymerizable functional group, Sp 2 is Sp 1 represents the same thing as defined in 12 X 11 (However, P 12 -Sp 2 , and Sp 2 -X 12does not include -OO-, -O-NH-, -SS- and -OS- groups; q2 represents 0 or 1, and * represents a bond to a carbon atom or another atom; the mesogenic group represented by MG above is represented by general formula (Me) above, and the mesogenic group may be substituted with a polymerizable functional group represented by general formula (P) above.
[0102] P 11 and P 12 are each preferably independently a group selected from the polymerizable groups represented by the following formulas (P-1) to (P-20).
[0103] [ka]
[0104] Among these polymerizable functional groups, from the viewpoint of enhancing polymerizability, the groups represented by the formulae (P-1), (P-2), (P-7), (P-12) and (P-13) are preferred, and the groups represented by the formulae (P-1) and (P-2) are more preferred.
[0105] Among the compounds represented by the above general formula (1), a monofunctional polymerizable liquid crystal compound having one polymerizable functional group in the molecule is preferred. As the monofunctional polymerizable liquid crystal compound having one polymerizable functional group in the molecule, a compound represented by the following general formula (1-1) is preferred.
[0106] [ka]
[0107] (In the above general formula (1-1), P 11 , Sp 1 , X 11 , q1, and MG are the same as those defined in the above general formula (1), and R 12represents a linear or branched alkyl group having 1 to 12 carbon atoms or a linear or branched alkenyl group having 1 to 12 carbon atoms, in which one -CH2- or two or more non-adjacent -CH2- may each be independently substituted with -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -NH-, -N(CH3)-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, and one or more hydrogen atoms in the alkyl group or alkenyl group may be substituted with a halogen atom or a cyano group, and when multiple substitutions are present, they may be the same or different.
[0108] Examples of the above general formula (1-1) include compounds represented by the following general formulas (1-1-1) to (1-1-4), but are not limited to these.
[0109] [ka]
[0110] In the above general formulas (1-1-1) to (1-1-4), P 11 , Sp 1 , X 11 , and q1 are the same as those defined in the above general formula (1), B9, B10, B11, B12, and B13 are the same as defined for B11 to B13 in general formula (Me) above, and may be the same or different. Z9, Z10, Z11, and Z12 are the same as Z11 to Z12 in the above general formula (Me), and may be the same or different. R 12represents a linear or branched alkyl group having 1 to 12 carbon atoms or a linear or branched alkenyl group having 1 to 12 carbon atoms, in which one -CH2- or two or more non-adjacent -CH2- are each independently substituted with -O-, -S-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -NH-, -N(CH3)-, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -CH=CH-, -CF=CF- or -C≡C-, and one or more hydrogen atoms in the alkyl group or alkenyl group may be substituted with a halogen atom or a cyano group, and when a plurality of substitutions are present, the substitutions may be the same or different.
[0111] Examples of the compounds represented by the above general formulas (1-1-1) to (1-1-4) include, but are not limited to, the compounds represented by the following formulas (1-1.1) to (1-1.26).
[0112] [ka]
[0113] [ka]
[0114] [ka]
[0115] [ka]
[0116] [ka]
[0117] In the above general formulas (1-1.1) to (1-1.26), R c represents a hydrogen atom or a methyl group, m represents an integer of 0 to 18, n represents 0 or 1, R 12 represents the same as the definition of the above general formulas (1-1.1) to (1-1.26), except that R 12 represents a hydrogen atom, a halogen atom, a cyano group, a linear alkyl group having 1 to 6 carbon atoms in which one -CH2- may be replaced by -O-, -CO-, -COO-, or -OCO-, or a linear alkenyl group having 1 to 6 carbon atoms, and the cyclic group (phenylene group, naphthylene group, or cyclohexylene group) in the above general formulas (1-1.1) to (1-2.26) may have, as a substituent, one or more of F, Cl, CF3, OCF3, CN group, alkyl group having 1 to 8 carbon atoms, alkoxy group having 1 to 8 carbon atoms, alkanoyl group having 1 to 8 carbon atoms, alkanoyloxy group having 1 to 8 carbon atoms, alkoxycarbonyl group having 1 to 8 carbon atoms, alkenyl group having 2 to 8 carbon atoms, alkenyloxy group having 2 to 8 carbon atoms, alkenoyl group having 2 to 8 carbon atoms, or alkenoyloxy group having 2 to 8 carbon atoms. Among the compounds represented by general formula (1), a bifunctional polymerizable liquid crystal compound having two polymerizable functional groups in the molecule is preferably a compound represented by the following general formula (1-2).
[0118] [ka]
[0119] (In the above general formula (1-2), P 11 , Sp 1 , X 11 , q1, M.G., X 12 , Sp 2 , q2, P 12 Each of them is the same as defined in the above general formula (1). Examples of the general formula (1-2) include compounds represented by the following general formulas (1-2-1) to (1-2-4), but are not limited to these.
[0120] [ka]
[0121] In the above general formulas (1-2-1) to (1-2-4), P 11 , Sp 1 , X 11 , q1, X 12 , Sp 2 , q2, P 12 Each of them is the same as defined in the above general formula (1), B9, B10, B11, B12, and B13 are the same as B11 to B13 in formula (P) above, and may be the same or different. Z9, Z10, Z11 and Z12 are the same as Z11 to Z12 in the above general formula (P), and may be the same or different.
[0122] Among the compounds represented by the above general formulas (1-2-1) to (1-2-4), it is preferable to use the compounds represented by the general formulas (1-2-2) to (1-2-4) having three or more ring structures in the compound, since the orientation of the obtained self-organized body is good and the curing properties are also good, and it is particularly preferable to use the compound represented by the general formula (1-2-2) having three ring structures in the compound.
[0123] Examples of the compounds represented by the above general formulas (1-2-1) to (1-2-4) include, but are not limited to, the compounds represented by the following formulas (1-2.1) to (1-2.21).
[0124] [ka]
[0125] [ka]
[0126] [ka]
[0127] [ka]
[0128] In the above general formulas (1-2.1) to (1-2.21), R d and R e each independently represents a hydrogen atom or a methyl group; The cyclic groups (phenylene groups, naphthylene groups, or cyclohexylene groups) in the above general formulae (1-2.1) to (1-2.21) may have, as a substituent, one or more of F, Cl, CF3, OCF3, CN groups, alkyl groups having 1 to 8 carbon atoms, alkoxy groups having 1 to 8 carbon atoms, alkanoyl groups having 1 to 8 carbon atoms, alkanoyloxy groups having 1 to 8 carbon atoms, alkoxycarbonyl groups having 1 to 8 carbon atoms, alkenyl groups having 2 to 8 carbon atoms, alkenyloxy groups having 2 to 8 carbon atoms, alkenoyl groups having 2 to 8 carbon atoms, and alkenoyloxy groups having 2 to 8 carbon atoms.
[0129] m1, m2, and m3 each independently represent an integer of 0 to 18; n1, n2, n3, and n4 each independently represent 0 or 1.
[0130] The liquid crystal compound having two polymerizable functional groups can be used alone or in combination with two or more other types, preferably from one to five types, and more preferably from two to five types.
[0131] The total content of bifunctional polymerizable liquid crystal compounds having two polymerizable functional groups in a molecule is preferably 10 to 100 mass %, more preferably 20 to 100 mass %, and particularly preferably 30 to 100 mass %, of the total amount of polymerizable liquid crystal compounds used in the polymerizable composition. As the polyfunctional polymerizable liquid crystal compound having three or more polymerizable functional groups, it is preferable to use a compound having three polymerizable functional groups. Among the compounds represented by the general formula (1), as the polyfunctional polymerizable liquid crystal compound having three polymerizable functional groups in the molecule, the compound represented by the following general formula (1-3) is preferable.
[0132] [ka] (In the above general formula (1-3), P 11 , Sp 1 , X 11 , q1, M.G., X 12 , Sp 2 , q2 are the same as those defined in the above general formula (1). 13 and P 14 each independently represents P in the above general formula (1-a). 12 It represents the same thing as the definition of X 13 is X in the above general formula (1). 11 represents the same thing as Sp 3 is Sp in the above general formula (1). 1 and q3 and q4 each independently represent 0 or 1. Examples of the above general formula (1-3) include compounds represented by the following general formulas (1-3-1) to (1-3-8), but are not limited to these.
[0133] [ka]
[0134] [ka]
[0135] In the above general formulas (1-3-1) to (1-3-8), P 11 , Sp 1 , X 11 , q1, M.G., X 12 , Sp 2 , q2, P 13 , X 13 , q4, Sp 3 , q3, P 14 are the same as those defined in the above general formula (1) and general formula (1-3), B9, B10, B11, B12, and B13 are the same as B11 to B13 in formula (P) above, and may be the same or different. Z9, Z10, Z11 and Z12 are the same as Z11 to Z12 in the above general formula (P), and may be the same or different.
[0136] Examples of the compounds represented by the above general formulas (1-3-1) to (1-3-8) include, but are not limited to, the compounds represented by the following formulas (1-3.1) to (1-3.6).
[0137] [ka]
[0138] [ka] In the above general formulas (1-3.1) to (1-3.6), R f , R g and R h each independently represents a hydrogen atom or a methyl group; R i , R j and R k each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a cyano group; when these groups are alkyl groups having 1 to 6 carbon atoms or alkoxy groups having 1 to 6 carbon atoms, they may all be unsubstituted or substituted with one or more halogen atoms; and the cyclic groups (phenylene groups or naphthylene groups) in the above general formulas (1-3.1) to (1-3.6) may have, as a substituent, one or more F, Cl, CF3, OCF3, CN groups, alkyl groups having 1 to 8 carbon atoms, alkoxy groups having 1 to 8 carbon atoms, alkanoyl groups having 1 to 8 carbon atoms, alkanoyloxy groups having 1 to 8 carbon atoms, alkoxycarbonyl groups having 1 to 8 carbon atoms, alkenyl groups having 2 to 8 carbon atoms, alkenyloxy groups having 2 to 8 carbon atoms, alkenoyl groups having 2 to 8 carbon atoms, and alkenoyloxy groups having 2 to 8 carbon atoms. m4 to m9 each independently represents an integer of 0 to 18; n4 to n10 each independently represents 0 or 1.
[0139] The polyfunctional polymerizable liquid crystal compound having three or more polymerizable functional groups can be used alone or in combination of two or more.
[0140] The total content of the polyfunctional polymerizable liquid crystal compounds having three or more polymerizable functional groups in the molecule is preferably 0 to 20 mass %, more preferably 0 to 15 mass %, and particularly preferably 0 to 10 mass %, of the total amount of the polymerizable liquid crystal compounds used in the polymerizable composition. -Combination of multiple polymerizable liquid crystal compounds- In the polymerizable composition of the present invention, it is preferable to use a mixture of multiple types of the above polymerizable liquid crystal compounds. The above-mentioned at least one or more monofunctional polymerizable liquid crystal compounds and at least one or more bifunctional polymerizable liquid crystal compounds and / or polyfunctional polymerizable liquid crystal compounds are preferably used in combination because the shape stability of the self-organized body obtained is also good, and it is more preferable to use at least one or more monofunctional polymerizable liquid crystal compounds and at least one or more bifunctional polymerizable liquid crystal compounds in combination. Among them, when it is desired to improve the shape stability of the self-organized body when the polymerizable composition of the present invention is used to form a self-organized body, it is preferable to use a compound selected from the above (1-2-2) to (1-2-4) having three or more ring structures in the compound as the bifunctional polymerizable liquid crystal compound to form a mixture of polymerizable liquid crystal compounds, and it is particularly preferable to use a mixture of the compound represented by the above (1-1-2) and the compound represented by the above (1-2-2) having three ring structures in the compound in combination.
[0141] The total amount of the monofunctional polymerizable liquid crystal compound and the bifunctional polymerizable liquid crystal compound is preferably 70% by mass to 100% by mass, and particularly preferably 80% by mass to 100% by mass, of the total amount of the polymerizable liquid crystal compounds used in the polymerizable composition.
[0142] <<Polymerizable discotic compounds>> In the polymerizable composition of the present invention, a polymerizable discotic liquid crystal compound exhibiting liquid crystallinity may be used as the polymerizable liquid crystal compound. The polymerizable composition of the present invention may also contain a non-liquid crystal polymerizable discotic compound.
[0143] The polymerizable discotic compound used in the present invention preferably has one or more polymerizable functional groups. Examples of such compounds include polymerizable compounds described in JP-A-7-281028, JP-A-7-287120, JP-A-7-333431, and JP-A-8-27284.
[0144] As the polymerizable liquid crystal compound, a long-shaped polymerizable liquid crystal compound (also referred to as a polymerizable rod-shaped liquid crystal compound) and a polymerizable discotic liquid crystal compound can be used in combination.
[0145] When a polymerizable rod-shaped liquid crystal compound and a polymerizable discotic liquid crystal compound are used in combination as the polymerizable liquid crystal compound, the total content of the polymerizable discotic liquid crystal compounds exhibiting liquid crystallinity is preferably 0 to 20 mass %, more preferably 0 to 15 mass %, and particularly preferably 0 to 10 mass %, of the total amount of the polymerizable liquid crystal compounds used in the polymerizable composition.
[0146] <<Polar solvent>> In the present invention, the polar solvent to be developed is not particularly limited as long as it is a poor solvent for the polymerizable liquid crystal compound, and is appropriately selected depending on the method for producing the self-assembled body. For example, the polar solvent is preferably water, a lower alcohol, or the like. In the present invention, the solubility parameter (SP value) of the polar solvent is 12.0 (cal / cm 3 ) 0.5 It is preferable that the calorie content is 13.0 (cal / cm 3 ) 0.5 More preferably, it is 22.0 (cal / cm 3 ) 0.5 More preferably, it is equal to or greater than this.
[0147] In the present invention, the polar solvent may be a mixed solvent, may contain a known salt, or may be a buffer solution, so long as it is a poor solvent for the polymerizable liquid crystal compound.
[0148] In the developing step of developing the polymerizable liquid crystal compound of the present invention in a polar solvent, the polymerizable liquid crystal compound may be dissolved in a first solvent different from the polar solvent to prepare a polymerizable composition containing the polymerizable liquid crystal compound, and then the polymerizable composition may be developed in the polar solvent. That is, in the present invention, the first solvent can be used as the developing solvent. It is preferable to use a developing solvent that has low solubility in the polar solvent and a boiling point lower than that of the polar solvent.
[0149] In the step of preparing a polymerizable composition containing a polymerizable liquid crystal compound and a first solvent and then spreading the polymerizable composition in a polar solvent, the solubility parameter SP value (cal / cm) of the first solvent that dissolves the polymerizable liquid crystal compound according to the Fedors method is 3 ) 0.5 and the solubility parameter SP value (cal / cm) of the polar solvent according to the Fedors method. 3 ) 0.5 The difference (absolute value) between the boiling point of the first solvent that dissolves the polymerizable liquid crystal compound and the boiling point of the polar solvent is preferably 11.00 or more and 17.0 or less, more preferably 11.5 or more and 16.5 or less, and even more preferably 12.0 or more and 16.5 or less. The difference (absolute value) between the boiling point of the first solvent that dissolves the polymerizable liquid crystal compound and the boiling point of the polar solvent is preferably 2°C or more and 50°C or less, more preferably 10°C or more and 45°C or less, and even more preferably 20°C or more and 45°C or less.
[0150] In the present invention, when the difference in solubility parameter as determined by the Fedors method and the difference in boiling point between the developing solvent and the developing solvent are within the above ranges, an L film can be easily formed on the developing solvent.
[0151] Generally, the solubility parameter (SP value) of organic solvents that dissolve polymerizable liquid crystal compounds is 13.0 (cal / cm 3 ) 0.5In the present invention, the solubility parameter (SP value) of the first solvent is preferably 12.0 or less, more preferably 11.5 or less, even more preferably 7.0 or more and less than 12.0, even more preferably 7.0 or more and less than 11.5, and even more preferably 7.0 or more and less than 11.5.
[0152] In the present invention, the SP value (solubility parameter / unit: (cal / cm 3 ) 0.5 ) refers to the solubility parameter calculated by the so-called Fedors method described in RF Fedors, Polymer Engineering and Science, 14(2), p147-154 (1974). In the Fedors method, the cohesive energy density and the molar volume are considered to depend on the type and number of the substituents, and the solubility parameter is expressed by the following (Formula 1). The solubility parameter is a value specific to each compound.
[0153]
number
[0154] (In the above formula (1), ΣE coh is the cohesive energy, and ΣV is the molar volume.) The SI unit of SP value is (J / cm 3 ) 0.5 or (MPa) 0.5 However, in this specification, the term (cal / cm 3 ) 0.5 The unit of SP value is expressed by the following formula: 1(cal / cm 3 ) 0.5 ≒2.05(J / cm 3 ) 0.5 ≒2.05(MPa) 0.5 ; can be converted.
[0155] Generally, the boiling point of the first solvent that dissolves the polymerizable liquid crystal compound is 100° C. or less, but in the present invention, the boiling point of the first solvent is preferably 90° C. or less, and more preferably 80° C. or less. The evaporation rate index of the first solvent is preferably 300 or more, more preferably 350 or more, and more preferably 400 or more.
[0156] The evaporation rate index mentioned above is an index showing the evaporation rate of each solvent when butyl acetate is set at 100, and conforms to the description in "Paint Flow and Pigment Dispersion" (translated and supervised by Kenji Ueki, published by Kyoritsu Shuppan Co., Ltd. on May 1, 1971) in "13.2 Solvent Evaporability" on page 294 and in Appendix B "Solvent Properties" at the end of the book.
[0157] In a preferred embodiment of the present invention, the first solvent, which is a developing solvent, has a solubility parameter (SP value) of 11.00 (cal / cm 3 ) 0.5 It is particularly preferable that the viscosity is 100 psig or less, the boiling point is 80° C. or less, and the evaporation rate index is 20 to 700. By using a solvent having the above physical properties as the first solvent, the solubility of the polymerizable liquid crystal compound and the developability in the polar solvent are excellent, and the solvent volatilizes immediately after development, so that the L film can be easily formed.
[0158] Specific examples of the first solvent in the present invention include ketone-based, acetate-based, hydrocarbon-based, glycol ether-based and ether-based organic solvents.
[0159] Examples of the ketone organic solvent include diisobutyl ketone, methyl isobutyl ketone, methyl propyl ketone, acetone, methyl ethyl ketone, cyclohexanone, and cyclopentanone.
[0160] Examples of the acetate-based organic solvent include isopropyl acetate, isobutyl acetate, butyl acetate, ethyl acetate, and gamma-butyrolactone.
[0161] Examples of the hydrocarbon organic solvent include toluene, xylene, hexane, heptane, and cyclohexane.
[0162] Examples of the glycol ether organic solvent include propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, and butyl carbitol.
[0163] As the first solvent, from the viewpoints of the solubility of the polymerizable liquid crystal compound and / or the (non-liquid crystal) polymerizable compound, the solubility in the developing solvent, and the solvent evaporation rate, it is preferable to use acetone, chloroform, 1,1,1-trichloroethane, hexane, heptane, tetrahydrofuran, methyl ethyl ketone, and ethyl acetate, and from the viewpoint of the hazardousness during handling, it is particularly preferable to use acetone and heptane. Note that the first solvent may be a mixed solvent as long as it does not impair the effects of the present invention.
[0164] The second solvent in the present invention is preferably a polar solvent and / or a solvent that undergoes phase separation from the first solvent, and is preferably, for example, a fluorine-based inert liquid (e.g., Fluorinert series). The solubility parameter SP value of the second solvent according to the Fedors method is 5.3 to 6.8 (cal / cm 3 ) 0.5 It is preferable that:
[0165] The range of the boiling point of the second solvent can be set in any combination depending on the mode of use, and is preferably, for example, 54°C to 220°C.
[0166] For example, preferred fluorine-based inert liquids include those having the following structures:
[0167] [ka]
[0168] [ka]
[0169] The polymerizable composition of the present invention may contain a non-liquid crystal polymerizable compound as necessary. By containing the non-liquid crystal polymerizable compound, the polymerizable liquid crystal compounds are easily linked to each other, and crosslinking property is improved, so that a self-assembled body having a highly ordered structure in which the molecular arrangement of the liquid crystal molecules is more controlled can be provided.
[0170] In the present invention, the non-liquid crystal polymerizable compound that may be contained in the polymerizable composition is preferably a photopolymerizable compound that is polymerized by irradiation with light, more preferably a photoradical polymerizable compound, and may be a photopolymerizable monomer or oligomer. These may be used together with a photopolymerization initiator. The photopolymerizable compound may be used alone or in combination of two or more kinds.
[0171] The non-liquid crystal polymerizable compound may be a (meth)acrylate compound. The (meth)acrylate compound may be a monofunctional (meth)acrylate having one (meth)acryloyl group, or a polyfunctional (meth)acrylate having a plurality of (meth)acryloyl groups.
[0172] In the polymerizable composition of the present invention, from the viewpoint of suppressing the disturbance of the molecular alignment of liquid crystal molecules and at the same time forming a self-organized body having a sufficient cross-linked structure, it is preferable to use a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate.
[0173] Examples of the monofunctional (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, dodecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, cyclohexyl (meth)acrylate, methoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate, nonylphenoxyethyl (meth)acrylate, glycidyl (meth)acrylate, dimethylaminoethyl ... ethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, benzyl (meth)acrylate, phenylbenzyl (meth)acrylate, succinic acid mono(2-acryloyloxyethyl), N-[2-(acryloyloxy)ethyl]phthalimide, N-[2-(acryloyloxy)ethyl]tetrahydrophthalimide, and the like.
[0174] The polyfunctional (meth)acrylate may be a difunctional (meth)acrylate, a trifunctional (meth)acrylate, a tetrafunctional (meth)acrylate, a pentafunctional (meth)acrylate, a hexafunctional (meth)acrylate, etc. For example, it may be a di(meth)acrylate in which two hydroxyl groups of a diol compound are substituted with (meth)acryloyloxy groups, or a di- or tri(meth)acrylate in which two or three hydroxyl groups of a triol compound are substituted with (meth)acryloyloxy groups.
[0175] Specific examples of the bifunctional (meth)acrylate include 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,5-pentanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, and 1,9-nonanediol di(meth)acrylate. acrylate, tricyclodecane dimethanol di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol hydroxypivalate diacrylate, tris(2-hydroxyethyl)isocyanurate di(meth)acrylates in which two hydroxyl groups of a diol obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol are substituted with (meth)acryloyloxy groups; di(meth)acrylates in which two hydroxyl groups of a diol obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A are substituted with (meth)acryloyloxy groups; di(meth)acrylates in which two hydroxyl groups of a triol obtained by adding 3 or more moles of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane are substituted with (meth)acryloyloxy groups; and di(meth)acrylates in which two hydroxyl groups of a diol obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A are substituted with (meth)acryloyloxy groups.
[0176] Specific examples of the trifunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate, glycerin triacrylate, pentaerythritol tri(meth)acrylate, and tri(meth)acrylate in which the three hydroxyl groups of a triol obtained by adding 3 or more moles of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane are substituted with (meth)acryloyloxy groups.
[0177] Specific examples of the tetrafunctional (meth)acrylate include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, and the like.
[0178] A specific example of the pentafunctional (meth)acrylate is dipentaerythritol penta(meth)acrylate.
[0179] A specific example of the hexafunctional (meth)acrylate is dipentaerythritol hexa(meth)acrylate.
[0180] In the polymerizable composition of the present invention, when the hardenable component is composed only of a photopolymerizable compound or contains the photopolymerizable compound as the main component, it is more preferable to use a polyfunctional photopolymerizable compound having two or more polymerizable functional groups in one molecule as the essential component, from the viewpoint of further improving the stability (strength over time, heat resistance, etc.) of the self-organized body.
[0181] The content of the non-liquid crystalline polymerizable compound in the polymerizable composition may be within a range that does not disrupt the molecular alignment, but is preferably 0 to 20 mass %, more preferably 0.5 to 15 mass %, and even more preferably 1 to 10 mass %.
[0182] The polymerizable composition of the present invention may contain a polymerization initiator as necessary. The polymerization initiator used in the polymerizable composition of the present invention is used to polymerize the polymerizable liquid crystal compound of the present invention. The polymerization initiator used when the polymerization step is carried out by light irradiation is not particularly limited, and any known and commonly used photopolymerization initiator can be used. The content of the photopolymerization initiator is preferably at a level that does not inhibit the alignment state or self-organization of the polymerizable liquid crystal compound used.
[0183] Examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone "Omnirad 184", 2-hydroxy-2-methyl-1-phenylpropanone "Omnirad 1173", 2-methyl-1-[(methylthio)phenyl]-2-morpholinopropane-1 "Omnirad 907", 2,2-dimethoxy-1,2-diphenylethan-1-one "Omnirad 651", 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl) -Butanone "Omnirad369", 2-Dimethylamino-2-(4-methylbenzyl)-1-(4-morpholino-phenyl)butan-1-one "Omnirad379", 2,2-Dimethoxy-1,2-diphenylethan-1-one, bis(2,4,6-trimethylbenzoyl)-diphenylphosphine oxide "OmniradTPO-H", 2,4,6-trimethylbenzoyl-phenyl-phosphine oxide "Omnirad819" (all from IGM Resins BV), 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], ethanone (Irgacure OXE01), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime) (Irgacure OXE02) (BASF Ltd.), a mixture of 2,4-diethylthioxanthone (Nippon Kayaku Co., Ltd.'s Kayacure DETX) and ethyl p-dimethylaminobenzoate (Nippon Kayaku Co., Ltd.'s Kayacure EPA), a mixture of isopropylthioxanthone (Ward Prekinsop's Cantacure ITX) and ethyl p-dimethylaminobenzoate (Esacure Examples of such photo-cationic initiators include "ESACURE ONE", "ESACURE KIP150", "ESACURE KIP160", "ESACURE 1001M", "ESACURE A198", "ESACURE KIP IT", "ESACURE KTO46", and "ESACURE TZT" (manufactured by Lamberti Co., Ltd.), and "Speed Cure BMS", "Speed Cure PBZ", and "Benzophenone" from LAMBSON. Furthermore, a photo-acid generator can be used as the photo-cationic initiator.Examples of the photoacid generator include diazodisulfone compounds, triphenylsulfonium compounds, phenylsulfone compounds, sulfonylpyridine compounds, triazine compounds, and diphenyliodonium compounds.
[0184] When the polymerizable composition of the present invention contains a photopolymerization initiator, the content of the photopolymerization initiator is preferably 0.1 to 10 mass%, particularly preferably 1 to 6 mass%, based on the total amount of the polymerizable liquid crystal compound and / or (non-liquid crystal) polymerizable compound contained in the polymerizable composition. The photopolymerization initiator can be used alone or in combination of two or more kinds. In addition, the photopolymerization initiator may not be contained. By not containing a photopolymerization initiator, effects such as improved stability of the liquid crystal exhibited by the polymerizable composition and improved storage stability can be obtained.
[0185] When dissolving a photopolymerization initiator in the polymerizable composition, it is preferable to dissolve the photopolymerization initiator in a non-liquid crystal polymerizable compound before use.
[0186] In order to dissolve the photopolymerization initiator in the non-liquid crystal polymerizable compound, it is preferable to add the photopolymerization initiator while stirring the non-liquid crystal polymerizable compound so as to uniformly dissolve the photopolymerization initiator, in order to prevent a reaction due to heat from being initiated.
[0187] The dissolution temperature of the photopolymerization initiator may be appropriately adjusted in consideration of the solubility of the polymerization initiator used in the polymerizable liquid crystal compound and / or the (non-liquid crystal) polymerizable compound and the thermal polymerizability of the polymerizable liquid crystal compound and / or the (non-liquid crystal) polymerizable compound. From the viewpoint of not initiating polymerization of the polymerizable liquid crystal compound and / or the (non-liquid crystal) polymerizable compound, the dissolution temperature is preferably 10 to 50°C, more preferably 10 to 40°C, and even more preferably 10 to 30°C.
[0188] A thermal polymerization initiator may be used during thermal polymerization. The polymerization initiator used when the polymerization step is carried out by heat is not particularly limited, and a known and commonly used thermal polymerization initiator may be used. The content of the thermal polymerization initiator is desirably at a level that does not inhibit the alignment state or self-organization of the polymerizable liquid crystal compound used. Examples of the thermal polymerization initiator include methyl acetoacetate peroxide, cumene hydroperoxide, benzoyl peroxide, bis(4-t-butylcyclohexyl) peroxydicarbonate, t-butyl peroxybenzoate, methyl ethyl ketone peroxide, 1,1-bis(t-hexylperoxy)3,3,5-trimethylcyclohexane, p-pentahydroperoxide, t-butyl hydroperoxide, dicumyl peroxide, isobutyl peroxide, di(3-methyl-3-methoxybutyl) peroxydicarbonate, 1, Examples of the usable compounds include organic peroxides such as 1-bis(t-butylperoxy)cyclohexane, azonitrile compounds such as 2,2'-azobisisobutyronitrile and 2,2'-azobis(2,4-dimethylvaleronitrile), azoamide compounds such as 2,2'-azobis(2-methyl-N-phenylpropionamidim) dihydrochloride, azoamide compounds such as 2,2'azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, and alkylazo compounds such as 2,2'azobis(2,4,4-trimethylpentane). When the polymerizable composition of the present invention contains a thermal polymerization initiator, the content of the thermal polymerization initiator is preferably 0.1 to 10 mass %, particularly preferably 1 to 6 mass %, based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The thermal polymerization initiator can be used alone or in combination of two or more kinds. In addition, the thermal polymerization initiator may not be used.
[0189] The polymerizable composition of the present invention may contain a polymerization inhibitor as necessary. Examples of the polymerization inhibitor include phenolic compounds such as p-methoxyphenol, cresol, t-butylcatechol, 3,5-di-t-butyl-4-hydroxytoluene, 2,2'-methylenebis(4-methyl-6-t-butylphenol), 2,2'-methylenebis(4-ethyl-6-t-butylphenol), 4,4'-thiobis(3-methyl-6-t-butylphenol), 4-methoxy-1-naphthol, and 4,4'-dialkoxy-2,2'-bi-1-naphthol; hydroquinone, methylhydroxyphenyl; quinone compounds such as N,N'-diphenyl-p-phenylenediamine, 4-aminodiphenylamine, N,N'-diphenyl-p-phenylenediamine, Ni-propyl-N'-phenyl-p-phenylenediamine, N-(1,2-dimethyl-2,4-diphenyl-p-phenylenediamine, N-(1,2-dimethyl-2,4-diphenyl-p-phenylenediamine), ...Amine compounds such as 3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, diphenylamine, N-phenyl-β-naphthylamine, 4,4'-dicumyl-diphenylamine, and 4,4'-dioctyl-diphenylamine; thioether compounds such as phenothiazine and distearyl thiodipropionate; 2,2,6,6-tetramethylpiperidine-1-oxyl free radical, 2,2,6,6-tetramethylpiperidine, 4- N-oxyl compounds such as hydroxy-2,2,6,6-tetramethylpiperidine-1-oxyl free radical; N-nitrosodiphenylamine, N-nitrosophenylnaphthylamine, N-nitrosodinaphthylamine, p-nitrosophenol, nitrosobenzene, p-nitrosodiphenylamine, α-nitroso-β-naphthol, N,N-dimethyl-p-nitrosoaniline, p-nitrosodiphenylamine, p-nitrosodimethylamine, p-nitroso-N,N-diethylamine, N-nitrosoethanol N-nitroso-di-n-butylamine, N-nitroso-Nn-butyl-4-butanolamine, N-nitroso-diisopropanolamine, N-nitroso-N-ethyl-4-butanolamine, 5-nitroso-8-hydroxyquinoline, N-nitrosomorpholine, N-nitroso-N-phenylhydroxylamine ammonium salt (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., "Q-1300"), nitrosobenzene, 2,4,6-tri-tert-butylnitrobenzene, N-nitroso-N-methyl- Examples of the nitroso-based compounds include p-toluenesulfonamide, N-nitroso-N-ethylurethane, N-nitroso-Nn-propylurethane, 1-nitroso-2-naphthol, 2-nitroso-1-naphthol, sodium 1-nitroso-2-naphthol-3,6-sulfonate, sodium 2-nitroso-1-naphthol-4-sulfonate, 2-nitroso-5-methylaminophenol hydrochloride, 2-nitroso-5-methylaminophenol hydrochloride, and Q-1301 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0190] The amount of the polymerization inhibitor added is preferably 0.01 to 1.0% by mass, more preferably 0.02 to 0.5% by mass, based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The polymerization inhibitor may be used alone or in combination of two or more kinds.
[0191] The polymerizable composition of the present invention may contain an antioxidant as necessary. Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate ("IRGANOX1010"), thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate ("IRGANOX1035"), octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate ("IRGANOX1076"), "IRGANOX1135", "IRGANOX1330", 4,6-bis(octylthiomethyl)-o-cresol ("IRGANOX1520L"), "IRGANOX1726", and "IRGANOX1726". ANOX245, IRGANOX259, IRGANOX3114, IRGANOX3790, IRGANOX5057, IRGANOX565 (all manufactured by BASF Ltd.); ADK STAB AO-20, ADK STAB AO-30, ADK STAB AO-40, ADK STAB AO-50, ADK STAB AO-60, ADK STAB AO-80 (all manufactured by ADEKA Corporation); JP-360, JP-308E, JPE-10 (all manufactured by Johoku Chemical Industry Co., Ltd.); Sumilizer BHT, Sumilizer BBM-S, Sumilizer GA-80 (all manufactured by Sumitomo Chemical Co., Ltd.).
[0192] The amount of the antioxidant added is preferably 0.01 to 2.0% by mass, more preferably 0.02 to 1.0% by mass, based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The antioxidant may be used alone or in combination of two or more kinds.
[0193] The polymerizable composition of the present invention may contain an ultraviolet absorber and / or a light stabilizer as necessary. The ultraviolet absorber or light stabilizer to be used is not particularly limited, but is preferably one that improves the light resistance of the self-assembled structure.
[0194] Examples of the ultraviolet absorber include 2-(2-hydroxy-5-t-butylphenyl)-2H-benzotriazole "TINUVIN PS", "TINUVIN 99-2", "TINUVIN 109", "TINUVIN 213", "TINUVIN 234", "TINUVIN 326", "TINUVIN 328", "TINUVIN 329", "TINUVIN 384-2", "TINUVIN 571", 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol "TINUVIN 900", 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol "TINUVIN 928", "TINUVIN 1130", "TINUVIN 400", and "TINUVIN 405", 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine, "TINUVIN 460", "TINUVIN 479", and "TINUVIN 5236" (all manufactured by BASF Ltd.), "ADK STAB LA-32", "ADK STAB LA-34", "ADK STAB LA-36", "ADK STAB LA-31", "ADK STAB 1413", and "ADK STAB LA-51" (all manufactured by ADEKA Corporation).
[0195] Examples of light stabilizers include "TINUVIN 111FDL", "TINUVIN 123", "TINUVIN 144", "TINUVIN 152", "TINUVIN 292", "TINUVIN 622", "TINUVIN 770", "TINUVIN 765", "TINUVIN 780", "TINUVIN 905", "TINUVIN 5100", "TINUVIN 5050", "TINUVIN 5060", "TINUVIN 5151", "CHIMASSORB 119FL", "CHIMASSORB 944FL", "CHIMASSORB 944LD" (all manufactured by BASF Ltd.), "ADK STAB LA-52", "ADK STAB LA-57", "ADK STAB LA-62", "ADK STAB LA-67", "ADK STAB LA-63P", "ADK STAB LA-68LD", "ADK STAB LA-77", "ADK STAB LA-82", and "ADK STAB LA-87" (all manufactured by ADEKA Corporation).
[0196] The amount of the ultraviolet absorber and / or light stabilizer added is preferably 0.001 to 1.0% by mass based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The ultraviolet absorber and / or light stabilizer may be used alone or in combination of two or more kinds.
[0197] The polymerizable composition of the present invention may contain a chain transfer agent as necessary. The chain transfer agent is a component that can obtain a uniform crosslinked structure and is used for the purpose of further improving the shape stability of the self-assembled body.
[0198] Examples of the chain transfer agent include aromatic hydrocarbons; halogenated hydrocarbons such as chloroform, carbon tetrachloride, carbon tetrabromide, and bromotrichloromethane; mercaptan compounds such as octyl mercaptan, n-butyl mercaptan, n-pentyl mercaptan, n-hexadecyl mercaptan, n-tetradecyl mercaptan, n-dodecyl mercaptan, t-tetradecyl mercaptan, and t-dodecyl mercaptan; hexanedithiol, decanedithiol, 1,4-butanediol bisthiopropionate, 1,4-butanediol bisthioglycolate, ethylene glycol bisthioglycolate, ethylene glycol bisthiopropionate, trimethylolpropane tristhioglycolate, trimethylolpropane tristhiopropionate, trimethylolpropane tris(3-mercaptobutyrate), pentaerythritol tetrakisthioglycolate, pentaerythritol tetrakisthioglycolate, and the like. Thiol compounds such as thiol tetrakisthiopropionate, trimercaptopropionic acid tris(2-hydroxyethyl)isocyanurate, 1,4-dimethylmercaptobenzene, 2,4,6-trimercapto-s-triazine, and 2-(N,N-dibutylamino)-4,6-dimercapto-s-triazine; sulfide compounds such as dimethylxanthogen disulfide, diethylxanthogen disulfide, diisopropylxanthogen disulfide, tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetrabutylthiuram disulfide; N,N-dimethylaniline, N,N-divinylaniline, pentaphenylethane, α-methylstyrene dimer, acrolein, allyl alcohol, terpinolene, α-terpinene, γ-terpinene, and dipentene, among which 2,4-diphenyl-4-methyl-1-pentene and thiol compounds are preferred.
[0199] Specific examples of the chain transfer agent include preferred compounds represented by the following general formulas (4-1) to (4-12).
[0200] [ka]
[0201] [ka]
[0202] In the above general formulas (4-1) to (4-2), R 45 represents an alkyl group having 2 to 18 carbon atoms, the alkyl group may be linear or branched, and one or more methylene groups in the alkyl group may be substituted with an oxygen atom, a sulfur atom, -CO-, -OCO-, -COO- or CH=CH- without the oxygen atoms and sulfur atoms being directly bonded to each other.
[0203] In the above general formulas (4-3) to (4-4), R 46 represents an alkylene group having 2 to 18 carbon atoms, and one or more methylene groups in the alkylene group may be substituted with an oxygen atom, a sulfur atom, -CO-, -OCO-, -COO- or CH=CH- without the oxygen atoms and sulfur atoms being directly bonded to each other.
[0204] The amount of the chain transfer agent added is preferably 0.1 to 10% by mass, more preferably 1.0 to 5% by mass, based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The chain transfer agent may be used alone or in combination of two or more kinds.
[0205] The polymerizable composition of the present invention may contain a sensitizer as necessary. As the sensitizer, amines that do not cause an addition reaction with the polymerizable liquid crystal compound and / or the (non-liquid crystal) polymerizable compound may be used. Examples of such sensitizers include trimethylamine, methyldimethanolamine, triethanolamine, p-diethylaminoacetophenone, ethyl p-dimethylaminobenzoate, isoamyl p-dimethylaminobenzoate, N,N-dimethylbenzylamine, and 4,4'-bis(diethylamino)benzophenone.
[0206] The amount of the sensitizer added is preferably 0.001 to 3 mass % based on the total amount of the polymerizable liquid crystal compound and the non-liquid crystal polymerizable compound contained in the polymerizable composition. The sensitizer may be used alone or in combination of two or more kinds. EXAMPLES
[0207] (Preparation of Polymerizable Composition 1) 50 parts by mass of a polymerizable liquid crystal compound represented by formula (A-1) described later, 50 parts by mass of a polymerizable liquid crystal compound represented by formula (A-2) described later, and 0.1 parts by mass of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 300 parts by mass of acetone, and then heated to 40°C and stirred to dissolve, to prepare a mixed solution 1. Then, after checking the dissolution state of the mixed solution 1, the temperature of the mixed solution 1 was returned to room temperature, and 1 part by mass of a photopolymerization initiator Omnirad651 (O-651: manufactured by IGM Resins BV) was further added and stirred to check the dissolution state, and then filtered through a 0.20 μm membrane filter to obtain a solution 1. The solution 1 was transparent and uniform. Furthermore, acetone was added to this solution 1 so that the solution concentration became 10 g / L, and a polymerizable composition 1 was obtained.
[0208] (Preparation of Polymerizable Composition 2) 100 parts by mass of a polymerizable liquid crystal compound represented by the formula (A-1) described later and 0.1 parts by mass of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 300 parts by mass of acetone, and then the mixture was heated to 40°C and stirred to dissolve, to prepare a mixed solution 2. Then, after checking the dissolution state of the mixed solution 2, the temperature of the mixed solution 2 was returned to room temperature, 1 part by mass of Omnirad651 was further added and stirred to check the dissolution state, and the mixture was filtered through a 0.20 μm membrane filter to obtain a solution 2. The solution 2 was transparent and uniform. Furthermore, acetone was added to this solution 2 so that the solution concentration became 10 g / L, and a polymerizable composition 2 was obtained.
[0209] (Preparation of Polymerizable Composition 3) Polymerizable composition 3 was obtained by preparation under the same conditions as polymerizable composition 1, except that the polymerizable liquid crystal compound represented by formula (A-1) described below was changed to a compound represented by formula (A-3) described below.
[0210] (Preparation of Polymerizable Composition 4) Polymerizable composition 4 was obtained by preparation under the same conditions as polymerizable composition 2, except that the polymerizable liquid crystal compound represented by formula (A-1) described below was changed to a compound represented by formula (B-1) described below.
[0211] (Preparation of Polymerizable Composition 5) Polymerizable composition 5 was obtained by preparation under the same conditions as polymerizable composition 1, except that the polymerizable liquid crystal compounds represented by formulas (A-1) and (A-2) described below were changed to polymerizable liquid crystal compounds represented by formulas (B-2) and (B-3) described below.
[0212] (Preparation of Polymerizable Composition 6) 47.5 parts by mass of a polymerizable liquid crystal compound represented by formula (A-2) described later, 47.5 parts by mass of a polymerizable liquid crystal compound represented by formula (A-3) described later, 5 parts by mass of a compound represented by formula (C-1) described later, and 0.1 parts by mass of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 300 parts by mass of acetone, and then heated to 40°C and stirred to dissolve, to prepare a mixed solution 6. Then, after confirming the dissolution state of the mixed solution 6, the temperature of the mixed solution 6 was returned to room temperature, 1 part by mass of Omnirad651 was further added and stirred to confirm the dissolution state, and the mixture was filtered through a 0.20 μm membrane filter to obtain a solution 6. The solution 6 was transparent and uniform. Furthermore, acetone was added to this solution 6 so that the solution concentration became 10 g / L, and a polymerizable composition 6 was obtained.
[0213] (Preparation of Polymerizable Composition 7) Polymerizable composition 7 was obtained by preparation under the same conditions as those for polymerizable composition 1, except that acetone was changed to chloroform.
[0214] (Preparation of Polymerizable Composition 8) 25 parts by mass of a polymerizable liquid crystal compound represented by formula (A-1) described later, 25 parts by mass of a polymerizable liquid crystal compound represented by formula (A-2) described later, 50 parts by mass of a compound represented by formula (B-3) described later, and 0.1 parts by mass of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 300 parts by mass of acetone, and then heated to 40°C and stirred to dissolve, to prepare a mixed solution 8. Then, after confirming the dissolution state of the mixed solution 8, the temperature of the mixed solution 8 was returned to room temperature, 1 part by mass of Omnirad651 was further added and stirred to confirm the dissolution state, and the mixture was filtered through a 0.20 μm membrane filter to obtain a solution 8. The solution 8 was transparent and uniform. Furthermore, acetone was added to this solution 8 so that the solution concentration became 10 g / L, and a polymerizable composition 8 was obtained.
[0215] (Preparation of Polymerizable Composition 9) 48 parts by mass of a polymerizable liquid crystal compound represented by formula (A-2) described later, 48 parts by mass of a polymerizable liquid crystal compound represented by formula (A-3) described later, 4 parts by mass of a compound represented by formula (C-2) described later, and 0.1 parts by mass of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.) were added to 300 parts by mass of acetone, and then heated to 40°C and stirred to dissolve, to prepare a mixed solution 9. Then, after confirming the dissolution state of the mixed solution 9, the temperature of the mixed solution 9 was returned to room temperature, 1 part by mass of Omnirad651 was further added and stirred to confirm the dissolution state, and the mixture was filtered through a 0.20 μm membrane filter to obtain a solution 9. The solution 9 was transparent and uniform. Furthermore, acetone was added to this solution 9 so that the solution concentration became 10 g / L, and a polymerizable composition 9 was obtained.
[0216] (Preparation of Polymerizable Composition 10) Polymerizable composition 10 was obtained by preparation under the same conditions as polymerizable composition 6, except that the polymerizable liquid crystal compound represented by formula (C-1) described below was changed to a compound represented by formula (B-4) described below.
[0217] (Preparation of Polymerizable Composition 11) Polymerizable composition 11 was obtained by preparing the polymerizable composition 5 under the same conditions as those for the polymerizable composition 5, except that Omnirad651 was not used.
[0218] (List of compounds used in the examples and comparative examples) The polymerizable liquid crystal compounds and non-liquid crystal polymerizable compounds used in the examples and comparative examples are as follows.
[0219] [ka]
[0220] Example 1 <Preparation and evaluation of self-organized body 1> After placing the glass substrate on the bottom of a petri dish (diameter 4 cm), pure water was poured into the petri dish in an amount sufficient to immerse the entire glass substrate. 2 The polymerizable composition 1 was spread on pure water with an aqueous phase temperature of 20°C in an amount such that the amount of the polymerizable composition 1 was 1.0 μm, and the acetone was evaporated to form an L film 1 (unpolymerized state) of the polymerizable composition 1. The L film 1 thus formed was observed using a depolarized reflected light microscope (DRLM) with a configuration shown in Figure 5. Figure 6 shows a polarizing microscope photograph of the L film 1 formed using the polymerizable composition 1. The L film 1 had the optical anisotropy of a smectic C phase, as shown in Figure 6. Furthermore, a high-pressure mercury lamp was used at a distance of 7 mm from the obtained L film 1 to illuminate the L film 1 with 1.59 mW / cm 2 A polymerization process was carried out by irradiating the L film 1 with ultraviolet light at an intensity of 100 nm for 5 minutes. The texture image, which showed a smectic C phase before UV irradiation, changed during UV irradiation and showed a dark state similar to a smectic A phase. This change took about 4 seconds after UV irradiation. After UV irradiation, the pure water was volatilized and removed at 90°C to produce self-assembled body 1 on the glass substrate. The self-assembled body 1 on the glass substrate was dissolved in tetrahydrofuran (THF) and sampled for GPC measurement, which confirmed that the molecular weight had increased, and polymerization had progressed due to UV irradiation. 5 shows, as an example of a reflective polarizing microscope, a configuration including a laser (λ=532 [nm]) 107, a polarizer 108, a lens 109, an analyzer 110, a lens 111, and a CCD camera 112. Also, in FIG. 5, a state in which liquid crystal molecules (or a polymerizable liquid crystal compound) 2 are irradiated with ultraviolet light using a UV lamp 114, whereby a self-organized body 113 made of liquid crystal molecules 2 forms a film on a polar solvent 5.
[0221] Example 2 <Preparation and evaluation of self-organized body 2> Except for changing the polymerizable composition 1 used in the above-mentioned Example 1 to the above-mentioned polymerizable composition 2, an L film 2 (unpolymerized state) was prepared in the same manner as in Example 1. When the L film 2 was observed with the reflective polarizing microscope used in Example 1, it had the optical anisotropy of a smectic A phase. Furthermore, it was irradiated with ultraviolet rays in the same manner as in Example 1. After the ultraviolet irradiation, the pure water was volatilized and removed at 90°C to prepare a self-assembled body 2 on a glass substrate. The self-assembled body 2 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased, and polymerization had progressed due to the ultraviolet irradiation.
[0222] Example 3 <Preparation and evaluation of self-organized body 3> An L film 3 (unpolymerized state) was prepared in the same manner as in Example 1, except that the polymerizable composition 1 used in Example 1 was changed to the above-mentioned polymerizable composition 3. When the L film 3 was observed with the reflective polarizing microscope used in Example 1, the L film 3 had the optical anisotropy of a hexatic phase, as shown in FIG. 7a. Furthermore, a high-pressure mercury lamp was used at a distance of 7 mm from the obtained L film 3, and a 1.59 mW / cm 2When a polymerization process was performed by irradiating the L film 3 with ultraviolet light at an intensity of 100 nm, it was confirmed that the texture image, which showed a hexatic phase before ultraviolet light irradiation, gradually changed during ultraviolet light irradiation (see Figures 7b and 7c). Then, 40 seconds after ultraviolet light irradiation, it showed a dark state similar to a smectic A phase (see Figure 7d). After ultraviolet light irradiation, the pure water was volatilized and removed at 90°C to produce a self-assembled body 3 on a glass substrate. The self-assembled body 3 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased, and polymerization had progressed due to ultraviolet light irradiation.
[0223] Example 4 <Preparation and evaluation of self-organized body 4> Except for changing the polymerizable composition 1 used in Example 1 to the above polymerizable composition 4, an L film 4 (unpolymerized state) was prepared in the same manner as in Example 1. When the L film 4 was observed with the reflective polarizing microscope used in Example 1, the L film 4 had optical anisotropy of a hexatic phase as shown in FIG. 8. Furthermore, when ultraviolet light was irradiated in the same manner as in Example 1, the texture changed during the ultraviolet light irradiation. After the ultraviolet light irradiation, pure water was volatilized and removed at 90°C to prepare a self-assembled body 4 on a glass substrate. The self-assembled body 4 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased and polymerization had progressed due to ultraviolet light irradiation.
[0224] Example 5 <Preparation and evaluation of self-organized body 5> Except for changing the polymerizable composition 1 used in Example 1 to the above polymerizable composition 5, an L film 5 (unpolymerized state) was prepared in the same manner as in Example 1. When the L film 5 was observed with the reflective polarizing microscope used in Example 1, the L film 5 had optical anisotropy of a smectic C phase as shown in FIG. 9. Furthermore, when ultraviolet light was irradiated in the same manner as in Example 1, it was confirmed that the texture changed during ultraviolet light irradiation as shown in FIG. 10. After ultraviolet light irradiation, pure water was volatilized and removed at 90°C to prepare a self-assembled body 5 on a glass substrate. The self-assembled body 5 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased and polymerization had progressed due to ultraviolet light irradiation.
[0225] Example 6 <Preparation and evaluation of self-organized body 6> An L film 6 (unpolymerized state) was prepared in the same manner as in Example 1, except that the polymerizable composition 1 used in Example 1 was changed to the above-mentioned polymerizable composition 6. When the L film 6 was observed with the reflective polarizing microscope used in Example 1, the L film 6 had optical anisotropy of a hexatic phase, as shown in FIG. 11. Furthermore, when ultraviolet light was irradiated in the same manner as in Example 1, the texture changed during ultraviolet light irradiation, as shown in FIG. 12. After ultraviolet light irradiation, pure water was volatilized and removed at 90°C to prepare a self-assembled body 6 on a glass substrate. The self-assembled body 6 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased and polymerization had progressed due to ultraviolet light irradiation.
[0226] Example 7 <Preparation and evaluation of self-organized body 7> An L film 7 (unpolymerized state) was prepared in the same manner as in Example 1, except that the polymerizable composition 1 used in Example 1 was changed to the above-mentioned polymerizable composition 7. When the L film 7 was observed with the reflective polarizing microscope used in Example 1, the L film 7 had optical anisotropy of a smectic C phase, as shown in FIG. 13. Furthermore, ultraviolet rays were irradiated in the same manner as in Example 1. After ultraviolet irradiation, pure water was volatilized and removed at 90°C to prepare a self-assembled body 7 on a glass substrate. The self-assembled body 7 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased, and polymerization had progressed due to ultraviolet irradiation.
[0227] Example 8 <Preparation and evaluation of self-organized body 8> Except for changing the polymerizable composition 1 used in Example 1 to the above polymerizable composition 8, an L film 8 (unpolymerized state) was prepared in the same manner as in Example 1. When the L film 8 was observed with the reflective polarizing microscope used in Example 1, the L film 8 had the optical anisotropy of a smectic C phase. Furthermore, ultraviolet rays were irradiated in the same manner as in Example 1. After the ultraviolet irradiation, the pure water was volatilized and removed at 90°C to prepare a self-assembled body 8 on a glass substrate. The self-assembled body 8 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased, and polymerization had progressed due to the ultraviolet irradiation.
[0228] Example 9 <Preparation and evaluation of self-organized body 9> The intensity of the ultraviolet light irradiated during the polymerization process is 0.32 to 1.85 mW / cm 2A self-organized body 9 was produced in the same manner as in Example 3, except that the above was changed to the above. Next, the irradiation time dependency of the reflected light intensity in the polymerization step when producing the self-organized body 9 was evaluated from the measurement of the image observed with the reflection type polarizing microscope used in Example 1. The evaluation results are shown in FIG. 14. FIG. 14 is an experimental result showing the relationship between the reflected light intensity and the (irradiation) time under various ultraviolet irradiation conditions in the polymerization step. As shown in FIG. 14, it is confirmed that the polymerization time is shortened when the ultraviolet light (or UV light) intensity in the polymerization step is increased. Furthermore, when the reflected light intensity at the start of ultraviolet light irradiation is set to 1, and the time from the irradiation of the ultraviolet light until the reflected light intensity reaches 0.1 is set as the relaxation time, it was confirmed that the ultraviolet light intensity and the relaxation time are inversely proportional to each other.
[0229] Example 10 <Relationship between surface pressure and molecular occupancy area> The experimental results showing the relationship between the surface pressure (π) and the molecular occupancy area (A) obtained using a Langmuir film preparation trough for the prepared polymerizable composition 1 are shown in Figure 15. As shown in Figure 15, the molecular occupancy area A>0.5 nm 2 In the region, no in-plane anisotropy is observed, and the molecular occupancy area A is 0.2 to 0.5 nm 2 In-plane anisotropy was confirmed in the region of A<0.2 nm. 2 In the region, in-plane anisotropy is observed and the domains are brightly observed, indicating that the molecular occupancy area A<0.2 nm 2 It was shown that in the region, the molecules are formed in two or more layers on the water surface.
[0230] Example 11 <Molecular Occupancy Area and Pretilt Angle> A quantity of pure water sufficient to immerse the entire glass substrate was poured into the petri dish, and the molecular occupancy area was 0.265 nm 2The polymerizable composition 3 was spread on pure water at an aqueous phase temperature of 20° C. in an amount such that the amount of the polymerizable composition 3 spread would be 100% by weight, and the acetone was evaporated to form an L film 11(a) (unpolymerized state) from the polymerizable composition 3. When the L film 11(a) was observed with the reflective polarizing microscope used in Example 1, the L film 11(a) exhibited the optical anisotropy of a smectic C phase as shown in FIG.
[0231] On the other hand, the molecular occupancy area is 0.196 nm 2 The polymerizable composition 3 was spread on pure water at an aqueous phase temperature of 20° C. in an amount such that the amount of the polymerizable composition 3 spread would be 100% by weight, and the acetone was evaporated to form an L film 11(b) (unpolymerized state) of the polymerizable composition 3. When the L film 11(b) was observed with the reflective polarizing microscope used in Example 1, the L film 11(b) exhibited the optical anisotropy of a hexatic phase as shown in FIG.
[0232] In addition, the L film (including unpolymerized and polymerized) in the present invention has a self-organized structure in which the surface direction of the L film intersects with the director of the mesogen part constituting the L film, and the mesogen parts are arranged in the surface direction of the L film. The molecular occupation area (A) and the pretilt angle of the molecules constituting the L film (unpolymerized state) will be explained with reference to Figs. 17(a) and 17(b). As described above, the pretilt angle represents the inclination of the mesogen molecule (an index showing that the surface direction of the film intersects with the director of the mesogen part constituting the film). More specifically, as described above, each of the pretilt angles βa and βb is the angle between the molecular long axis direction (director of the mesogen part) and the normal direction of the substrate 1. As shown in Figs. 17(a) and 17(b), the pretilt angle tends to increase as the molecular occupation area (A) increases. For example, the molecular occupancy area in Figure 17(a) is Aa (0.265 nm 2 ) and the molecular occupancy area Ab (0.196 nm 2 ) has a relationship of pretilt angle βa>pretilt angle βb.
[0233] Example 12 <Preparation and evaluation of self-organized body 12> Molecular occupancy area (A) is 0.156 to 0.222 nm 2 An L film 12 (unpolymerized state) was prepared in the same manner as in Example 11, except that the above conditions were changed to the above. The obtained L film 12 was subjected to a polymerization process under the same polymerization conditions as in Example 1 to prepare a self-assembled body 12, and the relationship between the relaxation time and the molecular occupancy area calculated from the image observed under a reflective polarizing microscope was evaluated by the measurement method of Example 9. The evaluation results are shown in FIG.
[0234] Example 13 <Preparation and evaluation of self-organized bodies 13 at liquid-liquid interfaces> After placing the glass substrate on the bottom of a petri dish (diameter 4 cm), a fluorine-based solvent (Fluorinert FC-40, manufactured by 3M Japan Ltd.) in an amount sufficient to immerse the entire glass substrate and pure water were poured into the petri dish and allowed to stand. 2 The polymerizable composition 5 was spread at a temperature of 20°C on the interface between the fluorinated solvent and pure water in an amount such that the amount of the polymerizable composition 5 would be 0.159 mW / cm. An L film 13 (unpolymerized state) was formed from the polymerizable composition 5. The obtained L film 13 was observed with the reflective polarizing microscope used in Example 1, and as shown in Figure 19, the L film 13 had the optical anisotropy of a smectic C phase. Furthermore, a high-pressure mercury lamp was used at a distance of 7 mm from the obtained L film 13 to illuminate the L film 13 with an optical anisotropy of 0.159 mW / cm. 2 When the L film 13 was irradiated with ultraviolet light at an intensity of 1000 nm for 5 minutes, the texture image, which showed a smectic C phase before the ultraviolet light irradiation, changed during the ultraviolet light irradiation and showed a dark state similar to a smectic A phase. As in Example 9, it was confirmed that the ultraviolet light intensity and the relaxation time are inversely proportional to each other, assuming that the reflected light intensity at the start of the ultraviolet light irradiation is 1 and the time from the ultraviolet light irradiation until the reflected light intensity reaches 0.1 is the relaxation time. After the ultraviolet light irradiation, the fluorine-based solvent and pure water were volatilized and removed at 90° C. to obtain a self-organized body 13 on the glass substrate. The self-organized body 13 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight increased and polymerization proceeded due to the ultraviolet light irradiation.
[0235] Example 14 <Preparation and evaluation of self-organized bodies 14 at liquid-liquid interfaces> Molecular occupancy area: 0.156~0.222nm 2 A self-assembled body 14 was prepared in the same manner as in Example 13, except for changing the above, and the relationship between the relaxation time calculated from the image observed with a reflection polarizing microscope and the molecular occupancy area was evaluated. The evaluation results are shown in FIG.
[0236] Example 15 <Fabrication of Liquid Crystal Display Element Using Self-Assembled Body 15> The electrode-attached substrate, which is a glass substrate, a transparent electrode film, and an interlayer insulating film (upper layer) in this order from the bottom, was placed in a petri dish with an amount of pure water that covered the entire electrode-attached substrate. 2 The polymerizable composition 6 was spread on pure water at an aqueous phase temperature of 20°C in an amount so that the amount of the polymerizable composition 6 was 1.59 mW / cm 2 , and the acetone was evaporated to form an L film 15 (unpolymerized state) from the polymerizable composition 6. A high-pressure mercury lamp was used at a distance of 7 mm from the obtained L film 15, and a 1.59 mW / cm 2 2 The L film 15 was irradiated with ultraviolet light at an intensity of 100 nm for 5 minutes. After the ultraviolet light irradiation, the pure water was volatilized and removed at 90° C. to produce a self-assembled body 15 on the electrode-attached substrate. A liquid crystal cell was produced using the electrode-attached substrate covered with the self-assembled body 15 produced, and an n-type liquid crystal composition was injected by a vacuum injection method to obtain a liquid crystal display element. When the pretilt angle of the liquid crystal display element was measured, it was confirmed that the self-assembled body 15 had a vertical alignment property and had an effect of controlling the alignment direction of liquid crystal molecules.
[0237] Example 16 <Observation of polymerization process of L-membrane using Brewster angle microscope (1)> The polymerization process of the L film 16 formed from the polymerizable composition 5 was observed using a Brewster angle microscope (hereinafter sometimes referred to as BAM), which can visualize the refractive index distribution of a film without in-plane anisotropy. The BAM is a microscope in which the angle of incidence is set to the Brewster angle of water. When a thin film with a refractive index different from that of water is spread on pure water, the Brewster angle changes and only the film is observed. By using the BAM, the polymerization state of the L film 16 could be observed in more detail.
[0238] Specifically, the L film 16 (unpolymerized state) prepared by the same method as in Example 5 above exhibited a smectic C phase with fluctuations. Then, a high-pressure mercury lamp was used to illuminate the L film 16 at a distance of 7 mm, and a 1.83 mW / cm 2 A polymerization step was carried out by irradiating the L film 16 with ultraviolet light for 5 minutes at an intensity of 100 nm. The state of polymerization at that time is shown in FIG.
[0239] Figure 21 shows a group of images of the film texture at various times after the start of UV irradiation, observed with a Brewster angle microscope. As shown in Figure 21, the texture changed during UV irradiation, the fluctuations disappeared, and the process of polymerization progressing was observed (see the image at 100 s in Figure 21). Moreover, in the texture 180 seconds after the start of UV irradiation (see the image at 180 s in Figure 21), unlike the aqueous phase, no fluctuations were observed, and the L film 16 after polymerization was clearly observed by BAM.
[0240] (Example 17) <Observation of polymerization process of L-membranes using Brewster angle microscopy (2)> The polymerization state of each L film 17 was observed by BAM under the same conditions as in Example 16, except that the molecular occupancy area was changed to various values. The molecular occupancy area values and the BAM observation images before and after polymerization are shown in Figures 22A and 22B. When the polymerizable composition 5 is used to form an L film, the molecular occupancy area is about 0.220 nm 2 When the molecular weight is larger, fine holes are formed in the polymerized film, and the molecular occupancy area is approximately 0.191 nm 2 When the molecular occupancy area is smaller than 0.191 nm, thicker (brighter) areas appear in the polymerized film. This indicates that the phase transition to three dimensions begins, and the thicker areas of the film are formed during polymerization, triggered by three-dimensional nuclei. 2 When the above condition is satisfied, a uniform film can be obtained.
[0241] (Example 18) <Relationship between molecular occupancy area and molecular order (1)> Molecular area of 0.278 nm 2 An L film 18 (unpolymerized state) was prepared in the same manner as in Example 6, except that the L film 18 was formed by using the same reflection polarizing microscope as in Example 1. When the L film 18 was observed with the reflection polarizing microscope used in Example 1, it was found that the L film 18 had the optical anisotropy of a smectic C phase, as shown in FIG. 23. From the results of Example 6, it was found that the molecular occupancy area was 0.2 nm 2 Since it was found that a hexatic phase was observed when the molecular occupancy area was 100%, this result, taken together with the results of Example 18, indicates that the degree of order of the molecular assembly state can be changed by changing the molecular occupancy area.
[0242] (Example 19) <Creation and evaluation of self-organized body 19> Except for changing the polymerizable composition 1 used in the above-mentioned Example 1 to the above-mentioned polymerizable composition 9, an L film 19 (unpolymerized state) was prepared in the same manner as in Example 1. When the L film 19 was observed with the reflective polarizing microscope used in Example 1, a bright pattern due to optical anisotropy was observed, and it was found to be in a liquid crystal state. Furthermore, the L film 19 was irradiated with ultraviolet light under the same conditions as in Example 1. The texture image, which showed a bright pattern due to optical anisotropy before ultraviolet light irradiation, changed during ultraviolet light irradiation and showed a dark state similar to the smectic A phase. This revealed that polymerization was also progressing in the polymerizable composition containing the polyfunctional non-liquid crystal polymerizable compound represented by the above-mentioned formula (C-2). The time required for this change was about 1 minute after ultraviolet light irradiation. After ultraviolet light irradiation, pure water was volatilized and removed at 90°C to prepare a self-organized body 19 on a glass substrate. The self-organized body 19 on the glass substrate was dissolved in THF and collected for GPC measurement, and it was confirmed that the molecular weight had increased and polymerization had progressed due to ultraviolet light irradiation.
[0243] (Example 20) <Preparation and evaluation of self-organized body 20> An L film 20 (unpolymerized state) was prepared in the same manner as in Example 1, except that the polymerizable composition 1 used in Example 1 was changed to the polymerizable composition 10. When the L film 20 was observed with the reflective polarizing microscope used in Example 1, the L film 20 had the optical anisotropy of a smectic C phase. Furthermore, ultraviolet light was irradiated to the L film 20 under the same conditions as in Example 1. The texture image, which exhibited the optical anisotropy of a smectic C phase before ultraviolet light irradiation, changed during ultraviolet light irradiation and showed a dark state similar to a smectic A phase, indicating that polymerization was progressing. The time required for this change was about 30 seconds after ultraviolet light irradiation. After ultraviolet light irradiation, pure water was volatilized and removed at 90°C to prepare a self-assembled body 20 on a glass substrate. The self-assembled body 20 on the glass substrate was dissolved in THF and collected for GPC measurement, confirming that the molecular weight had increased and that polymerization had progressed due to ultraviolet light irradiation.
[0244] Example 21 <Relationship between molecular occupancy area and molecular order (2)> Using the polymerizable composition 10, the molecular occupancy area was adjusted to various values (0.20 to 0.25 nm 2 ), an L film 21 (unpolymerized state) was prepared in the same manner as in Example 20. As a result, even if the molecular occupation area was changed, a hexatic liquid crystal phase was not observed, and a smectic C phase was observed regardless of the molecular occupation area. The reason for this is considered to be that the appearance of a relatively low-order liquid crystal phase such as a smectic C phase was stabilized by using a polymerizable liquid crystal compound of formula (B-4) having a molecular length close to that of the monofunctional components of formulas (A-2) and (A-3) as a bifunctional component in the polymerizable composition 10. In addition, when the water temperature was adjusted to 5°C and a similar experiment was performed as described above, the texture image, which exhibited the optical anisotropy of the smectic C phase before UV irradiation, changed during UV irradiation and exhibited a dark state similar to the smectic A phase, indicating that polymerization was proceeding even at temperatures lower than room temperature.
[0245] Example 22 <Preparation and evaluation of self-organized body 22> An L film 22 (unpolymerized state) was prepared in the same manner as in Example 1, except that the polymerizable composition 1 used in Example 1 was changed to the polymerizable composition 11. When the L film 22 was observed with the reflective polarizing microscope used in Example 1, it had the optical anisotropy of a smectic C phase. Furthermore, the L film 22 was irradiated with ultraviolet light under the same conditions as in Example 1. The texture image, which showed a bright pattern due to optical anisotropy before ultraviolet light irradiation, changed during ultraviolet light irradiation and showed a dark state similar to a smectic A phase. This revealed that polymerization was also progressing in the polymerizable composition that did not contain the photopolymerization initiator Omnirad651. It is believed that the irradiation of ultraviolet light on the L film 22 caused some molecules to generate radicals due to the ultraviolet light, and polymerization progressed because the film was made of single molecules. In addition, it is believed that the polymerization proceeded even without a photopolymerization initiator because the effect of p-methoxyphenol (MEHQ: manufactured by Tokyo Chemical Industry Co., Ltd.), which was used as a polymerization inhibitor, was weakened because it was a monomolecular film, or because it was dissolved in the water used to form the film, weakening its effect. [Explanation of symbols]
[0246] 1 Base material 2 Liquid crystal molecules (polymerizable liquid crystal compounds) 3. Mesogen section 4a molecular chain 4b molecular chain 5. Polar Solvents 6 Movable bar or partition plate 7. Air 100 Trough 101 Movable bar 102 Base material 103 Polymerizable liquid crystal compounds 104 Outlet 105 Polar Solvents 106 Placement table 107 Laser (λ=532[nm]) 108 Polarizer 109 Lens 110 Analyzer 111 Lens 112 CCD camera 113 Self-organized body 114 UV lamp
Claims
1. The following general formula (P): 【Chemistry 1】 (In the above general formula (P), P 10 represents a polymerizable functional group, Sp 10 represents an alkylene group having 1 to 18 carbon atoms; X 10 is -O-, -COO-, -OCO-, -OCH 2 --, --CH 2 O-, -CH 2 CH 2 OCO- or -CH 2 CH 2 COO-, q 10 represents 0 or 1; q 11 represents 0 or 1; q 10 +q 11 is 1 or 2 (where P 10 -Sp 10 , and Sp 10 -X 10 does not include -O-O-, -O-NH-, -S-S- and -O-S- groups. The P 10 represents any one of the following general formulas (P-1) to (P-20), 【Chemistry 2】 The polymerizable group moiety has a plurality of long mesogen moieties bonded together via a polymer chain formed by polymerization of two or more polymerizable group moieties represented by the formula: A self-organized structure in which the mesogen portions are self-organized so as to align with each other in a direction intersecting with the director of the mesogen portions.
2. the elongated mesogen portion is a group that induces an ordered structure; The self-organized structure according to claim 1, which is either a nanomaterial comprising a plurality of molecules selected from the group consisting of two-dimensional linear polymers, supramolecules (including micelles, vesicles or colloids), layered substances, membranes (including L-type membranes, L-type backbone membranes, and multilayer molecular membranes formed at an air-liquid interface (on the liquid surface)), polymer aggregates (including two-dimensional linear polymer aggregates), and membranous fragments, or a reactant formed by a chemical reaction between the molecules that constitute these nanomaterials.
3. The liquid crystal display device has a plurality of long mesogen portions bonded to each other via polymer chains derived from a polymerizable liquid crystal compound having a long mesogen portion and two or more polymerizable functional groups, A self-organized structure in which the mesogen parts are self-organized so as to be aligned in a direction intersecting with a director of the mesogen parts, The self-assembled structure according to claim 1 , wherein the polymerizable liquid crystal compound is represented by the following general formula (1): 【Chemistry 3】 [In the above general formula (1), P 11 represents the polymerizable functional group, Sp 1 represents an alkylene group having 1 to 18 carbon atoms (a hydrogen atom in the alkylene group may be substituted with one or more halogen atoms, a CN group, or an alkyl group having 1 to 8 carbon atoms and having a polymerizable functional group represented by the following general formula (1-a), and one CH 2 group or two or more non-adjacent CH 2 Each of the groups may be independently replaced by -O-, -COO-, -OCO- or -OCO-O-. 11 -O-, -S-, -OCH 2 --, --CH 2 O-, -CO-, -COO-, -OCO-, -CO-S-, -S-CO-, -O-CO-O-, -CO-NH-, -NH-CO-, -SCH 2 --, --CH 2 S-, -CF 2 O-, -OCF 2 -, -CF 2 S-, -SCF 2 -, -CH=CH-COO-, -CH=CH-OCO-, -COO-CH=CH-, -OCO-CH=CH-, -COO-CH 2 CH 2 --, --OCO-CH 2 CH 2 --, --CH 2 CH 2 -COO-, -CH 2 CH 2 -OCO-, -COO-CH 2 --, --OCO-CH 2 --, --CH 2 -COO-, -CH 2 represents —OCO—, —CH═CH—, —N═N—, —CH═N-N═CH—, —CF═CF—, —C≡C— or a single bond; q1 represents 0 or 1, MG represents a mesogenic group which may be substituted with a polymerizable functional group represented by formula (P), R 11 is represented by the following general formula (1-a): 【Chemistry 4】 (In the above general formula (1-a), P 12 represents a polymerizable functional group, Sp 2 is Sp 1 and X represents the same as defined in 12 , X 11 (However, P 12 -Sp 2 , and Sp 2 -X 12 does not include —O—O—, —O—NH—, —S—S— and —O—S— groups; q2 represents 1, and * represents a bond to a carbon atom or another atom; 【Chemistry 5】 (In the above general formula (P), P 10 represents a polymerizable functional group, Sp 10 represents an alkylene group having 1 to 18 carbon atoms; X 10 is -O-, -COO-, -OCO-, -OCH 2 --, --CH 2 O-, -CH 2 CH 2 OCO- or -CH 2 CH 2 COO-, q 10 represents 0 or 1; q 11 represents 0 or 1; q 10 +q 11 is 1 or 2. (However, P 10 -Sp 10 , and Sp 10 -X 10 does not include —O—O—, —O—NH—, —S—S— and —O—S— groups.
4. The self-organized body according to any one of claims 1 to 3, wherein the long mesogen portion has an optical axis in the long direction.
5. The self-organized body according to any one of claims 1 to 4, which is a film having a plurality of the long mesogen portions bonded via the polymer chains, wherein the surface direction of the film intersects with the director of the mesogen portions, and the mesogen portions are self-organized so as to be aligned in the surface direction of the film.
6. The self-organizing body according to claim 5 , which is formed by laminating two or more of the membrane bodies.
7. A substrate; A surface-modified substrate comprising: the self-assembly according to any one of claims 1 to 6 coated on the surface of the substrate.
8. A spreading step of spreading a polymerizable liquid crystal compound having a long mesogen portion in a polar solvent; a polymerization step of polymerizing the polymerizable liquid crystal compound; The method for producing a self-organized structure according to claim 1 , comprising:
9. The method according to claim 8 , further comprising a holding step of holding the mesogen portion of the polymerizable liquid crystal compound in a self-organized state by a first holding mechanism before or after the polymerization step.
10. The method according to claim 8 , wherein the polymerization step is a step of polymerizing the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is in contact with the polar solvent.
11. The manufacturing method according to any one of claims 8 to 10, wherein the polymerization step is a step of polymerizing the polymerizable liquid crystal compound in a state in which the polymerizable liquid crystal compound and the polar solvent are in contact with each other on a surface of the polar solvent and the polymerizable liquid crystal compound is spread on the surface.
12. a polymerization step of immersing a substrate in the polar solvent having the polymerizable liquid crystal compound spread on its surface after the spreading step, so that the polymerizable liquid crystal compound is attached to the substrate surface, and then polymerizing the polymerizable liquid crystal compound in a state where the polymerizable liquid crystal compound is in contact with the polar solvent; a recovery step of recovering a substrate having a surface formed with a self-assembled body in which a plurality of the long mesogen portions are bonded to each other via polymer chains by the polymerization step; The method according to any one of claims 8 to 11, comprising:
13. The manufacturing method described in claim 12, further comprising a holding step of holding the mesogenic portion of the polymerizable liquid crystal compound in a self-organized state by a first holding mechanism before or after the polymerization step, and the holding step is a step of transferring the self-organized polymerizable liquid crystal compound to the substrate by immersing the substrate in the polar solvent.
14. a first polymerization step in which the substrate is a substrate fed by a feed roll, and the polymerizable liquid crystal compound is polymerized in a state in which the polymerizable liquid crystal compound is in contact with the polar solvent by UV irradiation 1 before the polymerizable liquid crystal compound is applied to the surface of the substrate fed by the feed roll; and / or the substrate is a substrate fed by a feed roll, and the polymerizable liquid crystal compound is applied to the surface of the substrate fed by the feed roll, and then the polymerizable liquid crystal compound is polymerized by UV irradiation 2 in a state where the polymerizable liquid crystal compound is in contact with the polar solvent; The method according to claim 12 or 13, further comprising: a recovery step of recovering a substrate having on its surface the self-organized body in which a plurality of the long mesogen portions formed by the polymerization step are bonded via the polymer chains.
15. The method according to any one of claims 8 to 14, wherein the spreading step is a step of spreading a polymerizable composition containing the polymerizable liquid crystal compound and a first solvent in the polar solvent.
16. The solubility parameter SP value (cal / cm) of the first solvent according to the Fedors method 3 ) 0.5 and the solubility parameter SP value (cal / cm) of the polar solvent according to the Fedors method. 3 ) 0.5 The manufacturing method according to claim 15, wherein the absolute value of the difference between the boiling point of the first solvent and the boiling point of the polar solvent is 11.00 or more and 17.0 or less, and the absolute value of the difference between the boiling point of the first solvent and the boiling point of the polar solvent is 2 ° C. or more and 50 ° C. or less.
17. The solubility parameter SP value (cal / cm) of the first solvent according to the Fedors method 3 ) 0.5 The method according to claim 15 or 16, wherein the ratio of the saturation temperature to the saturation temperature is 11.50 or less.
18. The method according to any one of claims 8 to 17, further comprising a lamination step of laminating a self-organized body in which a plurality of the long mesogen moieties are bonded via polymer chains by the polymerization step.
Citation Information
Patent Citations
Manufacture of organic film
JP1988225604A
Liquid crystal optical element and production thereof
JP1991105314A
Production of thin film of heat resistant high polymer and production of liquid crystal oriented film
JP1991109972A
Manufacture of high-quality organic film
JP1993023577A
liquid crystal element
JP1993265005A